Polarizing element and its manufacturing method
The polarizing element, comprising a substrate, alignment film, and polarizing film cured in an orientation state, addresses the issue of peeling in flexible displays by enhancing flexural resistance.
Patent Information
- Application Number
- JP2021017704
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-05
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2041-02-05
AI Technical Summary
Existing polarizing elements used in flexible displays are prone to peeling when bent, due to insufficient flexural resistance.
A polarizing element is developed by stacking a substrate, an alignment film formed from an oriented polymer and a compound with active hydrogen reactive groups, and a polarizing film containing a polymerizable liquid crystal compound, active hydrogen-reactive groups, and dichroic dye, which are cured in an orientation state.
The proposed polarizing element exhibits enhanced flexural resistance, reducing the likelihood of peeling when bent, making it more suitable for use in flexible displays.
Smart Images

Figure 0007657064000001 
Figure 0007657064000002 
Figure 0007657064000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polarizing element, a method for producing said polarizing element, and a flat panel display and flexible display material comprising said polarizing element. [Background technology]
[0002] Polarizing plates are used by being attached to image display elements such as liquid crystal cells and organic EL display elements in image display devices typified by organic electroluminescence (hereinafter also referred to as organic EL) display devices. In recent years, with the demand for thinner image display devices, further thinner polarizing plates and polarizing films, which are one of the components of the image display devices, are also required, and various polarizing plates and polarizing films have been proposed to meet such demands. For example, Patent Document 1 discloses an ultra-thin polarizing element in which a polarizing layer made of oriented polymerizable liquid crystal compounds and dichroic dyes is provided on a substrate via a photoalignment layer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-102479 A Summary of the Invention [Problem to be solved by the invention]
[0004] Ultra-thin polarizing elements are expected to be suitable for use in flexible displays, etc. However, when the bending diameter becomes small, peeling of the polarizing film or the like may occur at the bending portion, and therefore, a polarizing element having high bending resistance that is more suitable for use in flexible displays is required.
[0005] An object of the present invention is to provide a polarizing element that is less likely to peel off when bent. [Means for solving the problem]
[0006] The present inventors have conducted extensive research to solve the above problems and have completed the present invention. [1] A polarizing element comprising a substrate, an alignment film, and a polarizing film laminated in this order, The alignment film is An oriented polymer (A-1), and Compound having an active hydrogen reactive group (A-2) A polarizing element, which is an alignment film formed by curing a composition for forming an alignment film comprising the above-mentioned. [2] The polarizing film is Polymerizable liquid crystal compound (B-1) A compound (B-2) having an active hydrogen reactive group, and Dichroic dye (B-3) The polarizing element according to [1] above, which is a polarizing film obtained by curing a composition for forming a polarizing film comprising: [3] The polarizing element according to the above [1] or [2], wherein the compound (A-2) further has an active hydrogen-containing group. [4] The polarizing element according to any one of the above [1] to [3], wherein the orientable polymer (A-1) is a polymer having a photoreactive group that causes a dimerization reaction. [5] The polarizing element according to any one of the above [1] to [4], wherein the orienting polymer (A-1) is a (meth)acrylic polymer. [6] The polarizing element according to any one of the above [1] to [5], wherein the weight average molecular weight of the orienting polymer (A-1) is 10,000 or more and 1,000,000 or less. [7] The polarizing element according to any one of the above [1] to [6], wherein the compound (A-2) is a silane coupling agent. [8] The polarizing element according to any one of the above [1] to [7], wherein the compound (A-2) is a silane coupling agent containing at least one functional group selected from the group consisting of a primary amino group, a secondary amino group, a hydroxyl group, and a mercapto group. [9] The polarizing element according to any one of the above [1] to [8], wherein the content of the compound (A-2) is from 1 part by mass to 30 parts by mass per 100 parts by mass of the orientable polymer (A-1).
[10] The polarizing element according to any one of the above [2] to [9], wherein the compound (B-2) further has a polymerizable group.
[11] The polarizing element according to
[10] above, wherein the polymerizable group is a (meth)acryloyl group.
[12] The polarizing element according to any one of the above [2] to
[11] , wherein the compound (B-2) has at least one isocyanate group and at least one (meth)acryloyl group.
[13] The polarizing element according to any one of the above [2] to
[12] , wherein the content of the compound (B-2) is 0.1 parts by mass or more and 12 parts by mass or less per 100 parts by mass of the polymerizable liquid crystal compound (B-1).
[14] The dichroic dye (B-3) has the formula (I): K 1 (-N=NK 2 ) p -N=NK 3 (I) [In formula (I), K 1 and K. 3 represent each independently a phenyl group which may be substituted, a naphthyl group which may be substituted, a phenyl benzoate group which may be substituted, or a monovalent heterocyclic group which may be substituted, K 2 represents an optionally substituted p-phenylene group, an optionally substituted naphthalene-1,4-diyl group, an optionally substituted 4,4'-stilbenylene group, or an optionally substituted divalent heterocyclic group, p represents an integer of 0 to 4, and when p is an integer of 2 or more, a plurality of K 2 may be the same or different, and the -N=N- bond may be replaced with a -C=C-, -COO-, -NHCO-, or -N=CH- bond so long as the compound exhibits absorption in the visible region. The polarizing element according to any one of the above [2] to
[13] , comprising a compound represented by the following formula:
[15] The polarizing element according to any one of the above [2] to
[14] , wherein the polymerizable liquid crystal compound (B-1) is a liquid crystal compound exhibiting smectic liquid crystallinity.
[16] The polarizing element according to any one of the above [1] to
[15] , wherein the thickness of the substrate is 1 μm or more and 10 μm or less.
[17] The polarizing element according to any one of the above [1] to
[16] , further comprising an overcoat layer on the surface of the polarizing film opposite to the alignment film.
[18] A method for producing a polarizing element comprising laminating a substrate, an alignment film, and a polarizing film in this order, comprising the steps of: (1) a step of forming a coating film of an alignment film-forming composition containing an alignment polymer (A-1) and a compound (A-2) having an active hydrogen reactive group on a substrate having a polar group, and drying the coating film to react the active hydrogen reactive group of the compound (A-2) with the polar group of the substrate to form a bond; (2) forming an alignment layer by subjecting the dried coating film obtained in step (1) to a rubbing treatment or light irradiation; (3) forming a coating film of a polarizing film-forming composition containing a polymerizable liquid crystal compound (B-1), a compound having an active hydrogen reactive group (B-2), and a dichroic dye (B-3) on the alignment film obtained in the step (2), and drying the coating film; and (4) A step of curing the polymerizable liquid crystal compound (B-1) and the dichroic dye (B-3) in the dried coating film obtained in step (3) in an aligned state to form a polarizing film. A manufacturing method comprising:
[19] The method according to
[18] above, further comprising the step of forming an overcoat layer on the polarizing film formed in step (4).
[20] A flat panel display device comprising the polarizing element according to any one of [1] to
[17] above.
[21] A flexible display material comprising the polarizing element according to any one of [1] to
[17] above. Effect of the Invention
[0007] According to the present invention, it is possible to provide a polarizing element which is unlikely to peel off when bent. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, the embodiments of the present invention will be described in detail. Note that the scope of the present invention is not limited to the embodiments described here, and various modifications can be made without departing from the spirit of the present invention.
[0009] The polarizing element of the present invention includes a substrate, an alignment film, and a polarizing film in this order. In the polarizing element of the present invention, the substrate, the alignment film, and the polarizing film are preferably adjacent to each other, so that the effects of the present invention can be more easily achieved. In addition to the substrate, the alignment film, and the polarizing film, the polarizing element of the present invention may further include other layers, as long as they do not affect the effects of the present invention. Examples of the other layers include an overcoat layer provided on the polarizing film, and an adhesive layer for bonding to an image display element such as a liquid crystal cell or an organic EL display element.
[0010] <Alignment film> The polarizing element of the present invention includes an alignment film obtained by curing an alignment film-forming composition containing an orientable polymer (A-1) and a compound (A-2) having an active hydrogen reactive group. In the present invention, the alignment film has an alignment control force that causes the liquid crystal alignment of the polymerizable liquid crystal compound and dichroic dye constituting the polarizing film described below in a desired direction, and a precisely oriented polarizing film can be easily obtained by applying a composition for forming a polarizing film containing a polymerizable liquid crystal compound, etc., onto the alignment film.
[0011] The state of liquid crystal alignment, such as horizontal alignment, vertical alignment, hybrid alignment, and tilt alignment, can be controlled by the properties of the alignment film and the polymerizable liquid crystal compound, and in the present invention, the combination can be arbitrarily selected according to the desired alignment state. For example, by using an alignment film formed from a material that exhibits horizontal alignment as an alignment control force, the polymerizable liquid crystal compound can be horizontally aligned or hybrid aligned, and by using an alignment film formed from a material that exhibits vertical alignment, the polymerizable liquid crystal compound can be vertically aligned or tilted aligned. The alignment directions, such as horizontal alignment and vertical alignment, refer to the long axis direction of the aligned polymerizable liquid crystal compound when the polarizing film plane is used as a reference. For example, horizontal alignment refers to a state in which the long axis direction of the aligned polymerizable liquid crystal compound is parallel to the polarizing film plane, and vertical alignment refers to a state in which the long axis direction of the aligned polymerizable liquid crystal compound is perpendicular to the polarizing film plane. Here, "horizontal to the polarizing film plane" refers to 0°±20° to the polarizing film plane, and "vertical" refers to 90°±20° to the polarizing film plane.
[0012] In the present invention, the alignment film is formed from an alignment film-forming composition containing an alignment polymer (A-1). The alignment regulating force of the alignment film can be arbitrarily controlled by the surface state, rubbing state, polarized light irradiation conditions, etc., depending on the type of alignment polymer (A-1) contained in the alignment film-forming composition. In addition, the liquid crystal alignment can be controlled by selecting the physical properties such as the surface tension and liquid crystallinity of the polymerizable liquid crystal compound.
[0013] The alignment film is preferably insoluble in a solvent used when forming a polarizing film on the alignment film, and has heat resistance during removal of the solvent and heat treatment for alignment of liquid crystal. Examples of the alignment film include a rubbing alignment film, a photo-alignment film, and a groove alignment film formed from an orienting polymer. In one embodiment of the present invention, the alignment film is preferably a photo-alignment film, from the viewpoints of easy control of the alignment direction during manufacture of the polarizing element and excellent accuracy and quality of the alignment angle.
[0014] When the alignment film is a rubbed alignment film formed from an alignment polymer, examples of the alignment polymer (A-1) include polyamides and gelatins having an amide bond in the molecule, polyimides having an imide bond in the molecule, and polyamic acids, which are hydrolyzates thereof, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinylpyrrolidone, polyacrylic acid, and polyacrylic acid esters. Hereinafter, the alignment polymer for the rubbed alignment film is also referred to as a "rubbed alignment polymer". Among them, polyvinyl alcohol is preferred as the rubbed alignment polymer. The rubbed alignment polymer may be used alone or in combination of two or more kinds.
[0015] When the alignment film is a photo-alignment film, the alignment polymer (A-1) is usually an alignment polymer having a photoreactive group. Hereinafter, the alignment polymer for forming the photo-alignment film is also referred to as a "photo-alignment polymer". In this specification, the photoreactive group refers to a group that generates liquid crystal alignment ability by light irradiation, and in the polymer that forms the photo-alignment film, the photoreactive group contributes to imparting liquid crystal alignment ability by the action of light. Specifically, it means a group that generates a photoreaction that is the origin of liquid crystal alignment ability by light irradiation, such as a dimerization reaction, an isomerization reaction, a photocrosslinking reaction, or a photodecomposition reaction, and induces the orientation of polymer molecules. The photoreactive group possessed by the photo-alignment polymer may be one type or two or more types.
[0016] As the photoreactive group capable of causing the above-mentioned reaction, those having an unsaturated bond, particularly a double bond, are preferable, and examples thereof include groups having at least one bond selected from the group consisting of a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond), and a carbon-oxygen double bond (C=O bond).
[0017] Examples of groups having a C=C bond include vinyl groups, polyene groups, stilbene groups, stilbazole groups, stilbazolium groups, chalcone groups, and cinnamoyl groups. Examples of groups having a C=N bond include groups having structures such as aromatic Schiff bases and aromatic hydrazones. Examples of groups having an N=N bond include azobenzene groups, azonaphthalene groups, aromatic heterocyclic azo groups, bisazo groups, formazan groups, and groups having azoxybenzene as a basic structure. Examples of groups having a C=O bond include benzophenone groups, coumarin groups, anthraquinone groups, and maleimide groups. These groups may have substituents such as alkyl groups, alkoxy groups, aryl groups, allyloxy groups, cyano groups, alkoxycarbonyl groups, hydroxyl groups, sulfonic acid groups, and halogenated alkyl groups. In particular, from the viewpoint of excellent alignment properties and reactivity, the photoalignable polymer preferably has a photoreactive group that undergoes a dimerization reaction or a photocrosslinking reaction, and more preferably has a photoreactive group that undergoes a dimerization reaction.
[0018] The dimerization reaction is a reaction in which an addition reaction occurs between two groups by the action of light, typically forming a ring structure. The group that causes such a dimerization reaction is a group containing a carbon-carbon double bond (C=C bond) or a carbon-oxygen double bond (C=O bond) that causes a dimerization reaction by light irradiation, and examples thereof include a group having a cinnamoyl structure, a group having a chalcone structure, a group having a coumarin structure, a group having a benzophenone structure, and a group having an anthracene structure. Among them, a group having a cinnamoyl structure and a group having a chalcone structure are preferred, and a group having a cinnamoyl structure is more preferred, because they are easy to control the reactivity and have excellent alignment control force during photoalignment. In addition, the group having the above structure is also advantageous in that the amount of polarized light irradiation required for photoalignment is relatively small, and a photoalignment film having excellent thermal stability and stability over time can be easily obtained.
[0019] The photoalignable polymer preferably has a photoreactive group that undergoes a dimerization reaction at the end of the polymer side chain, more preferably has a group having a cinnamoyl structure or a group having a chalcone structure at the end of the polymer side chain, and even more preferably has a group having a cinnamoyl structure at the end of the polymer side chain. Examples of such photoalignable polymers include polymers having a structure represented by the following formula (A1') and / or a structure represented by the formula (A1'') at the side chain (hereinafter, these are also collectively referred to as "photoalignable polymer (A)").
[0020] [ka] [In formula (A1') and formula (A1''), k represents 0 or 1. L 1 represents a single bond or -O-. L 2 represents a single bond, -O-, -COO-, -OCO-, -N=N-, -CH=CH- or -CH2-. R 1 , R 2 and R 3 each independently represents a hydrogen atom, a halogen atom, a halogenated alkyl group, a halogenated alkoxy group, a cyano group, a nitro group, an alkyl group, an alkoxy group, an aryl group, an allyloxy group, an alkoxycarbonyl group, a carboxyl group, a sulfonic acid group, an amino group, or a hydroxyl group, and the carboxyl group and the sulfonic acid group may form a salt with an alkali metal ion. R 4 represents a hydrogen atom, an alkyl group, or a phenyl group. * represents a bond to the polymer main chain.]
[0021] L in formula (A1') and formula (A1'') 2 When is any one of -O-, -COO-, -OCO-, -N=N-, -C=C- and -CH2-, the production of the photoalignable polymer (A) becomes easy.
[0022] R in formula (A1') and formula (A1'') 1 , R 2 and R 3 are preferably each independently a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms. 1 , R 2 and R 3 Examples of the alkyl group represented by the formula (I) include a methyl group, an ethyl group, and a butyl group, and examples of the alkoxy group include a methoxy group, an ethoxy group, and a butoxy group.
[0023] The main chain of the photo-oriented polymer (A) is not particularly limited, and examples of the structure of the monomer unit forming the main chain include those selected from the group consisting of (meth)acrylic acid ester units represented by formula (M-1) or formula (M-2); (meth)acrylamide units represented by formula (M-3) or formula (M-4); vinyl ether units represented by formula (M-5) or formula (M-6); (methyl)styrene units represented by formula (M-7) or formula (M-8), and vinyl ester units represented by formula (M-9) or formula (M-10). In formulas (M-1) to (M-10), * represents a bond to the structure represented by formula (A1') or formula (A1''), or a bond to a spacer unit described later. In this specification, the "main chain of the photoalignable polymer (A)" refers to the longest molecular chain among the molecular chains possessed by the photoalignable polymer (A).
[0024] [ka]
[0025] The main chain of the photoalignable polymer (A) may be a homopolymer formed from one type of monomer unit, or a copolymer formed from two or more types of monomer units. When the main chain of the photoalignable polymer (A) is a copolymer, it may have any bonding pattern such as an alternating type, a block type, a random type, or a graft type.
[0026] The structure of the monomer unit forming the main chain of the photoalignable polymer (A) may be a siloxane structure containing repeating units represented by formulas (M-11) to (M-16). In formulas (M-11) to (M-16), * represents a bond to the structure represented by formula (A1') or formula (A1''), or a bond to the spacer unit described below. [ka]
[0027] In formulas (M-11) to (M-16), R 5 R represents a bond to another silicon atom via an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an oxygen atom. 3 Examples of the alkyl group having 1 to 6 carbon atoms represented by the formula (I) include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, and an n-butyl group, and among these, a methyl group and an ethyl group are preferred. 5 Examples of the alkoxy group having 1 to 6 carbon atoms represented by the formula (I) include a methoxy group, an ethoxy group, an n-propyloxy group, an isopropyloxy group, an n-butoxy group, and the like. Among these, a methoxy group and an ethoxy group are preferable.
[0028] In formulae (M-13) and (M-14), Ph represents a divalent benzene ring (e.g., a phenylene group, etc.) which may have a substituent. In formula (M-16), Cy represents a divalent cyclohexane ring (e.g., a cyclohexane-1,4-diyl group, etc.) which may have a substituent.
[0029] n represents an integer of 1 to 4.
[0030] The main chain of the photoalignable polymer (A) is preferably composed of a structural unit represented by any one of formulas (M-1) to (M-16), more preferably composed of a structural unit represented by any one of formulas (M-1) to (M-10), and even more preferably composed of a structural unit selected from the group consisting of (meth)acrylic acid ester units and (meth)acrylamide units represented by formulas (M-1) to (M-4).
[0031] The monomer structural unit forming the main chain of the photoalignable polymer (A) represented by any one of formulas (M-1) to (M-16) may be directly bonded to the group represented by formula (A1') or formula (A1''), or may be bonded via a linking group which is a suitable spacer unit. When bonded via a linking group, examples of the linking group include a carbonyloxy group (ester bond), an oxygen atom (ether bond), an imide group, a carbonylimino group (amide bond), an iminocarbonylimino group (urethane bond), a divalent aliphatic hydrocarbon group which may have a substituent, a divalent aromatic hydrocarbon group which may have a substituent, and a divalent group formed by combining these. Examples of the divalent aromatic hydrocarbon group which may have a substituent include a phenylene group, a 2-methoxy-1,4-phenylene group, a 3-methoxy-1,4-phenylene group, a 2-ethoxy-1,4-phenylene group, a 3-ethoxy-1,4-phenylene group, and a 2,3,5-trimethoxy-1,4-phenylene group. Among these, an aliphatic hydrocarbon group is preferable, and an alkanediyl group having 1 to 11 carbon atoms which may have a substituent is more preferable. Examples of the alkanediyl group include a methylene group, an ethylene group, a trimethylene group, a tetramethylene group, a pentamethylene group, a hexamethylene group, a heptamethylene group, an octamethylene group, a nonamethylene group, a decamethylene group, and an undecamethylene group, which may be linear or branched. Examples of the substituent which the alkanediyl group may have include an alkoxy group having 1 to 4 carbon atoms.
[0032] The structure represented by formula (A1') is preferably used as a structural unit represented by (A1-1) (hereinafter also referred to as "structural unit (A1-1)") to form the photoalignable polymer (A), and in one embodiment of the present invention, the photoalignable polymer (A) contains the structural unit (A1-1). The structure represented by formula (A1'') is preferably used as a structural unit represented by (A1-2) (hereinafter also referred to as "structural unit (A1-2)") to form the photoalignable polymer (A), and in one embodiment of the present invention, the photoalignable polymer (A) contains the structural unit (A1-2). [ka]
[0033] In formula (A1-1) and formula (A1-2), L 1 , L 2 , R 1 , R 2 , R 3 , R 4 and k are the same as those in the formula (A1') or (A1''), and SP 1 is an alkanediyl group having 1 to 11 carbon atoms which may have a substituent, M 1 The structure represented by the formula (M-1) is a structure represented by any one of the formulas (M-1) to (M-16).
[0034] The photo-alignable polymer (A) may have a carboxyl group in addition to a photoreactive group, particularly a photoreactive group that causes a dimerization reaction. The photo-alignable polymer (A) having a photoreactive group and a carboxyl group may be, for example, a polymer consisting of a structural unit (A1-1), or, as another embodiment, may be one that includes a structural unit (A1-3) (hereinafter also referred to as "structural unit (A1-3)") in addition to the structure represented by formula (A1'), the structure represented by formula (A1''), or the structural unit (A1-1) and / or the structural unit (A1-2). [ka]
[0035] In formula (A1-3), l represents 0 or 1, and SP 2 represents an alkanediyl group having 1 to 11 carbon atoms which may have a substituent. SP 2 Specific examples of SP 1 are the same as the specific examples of SP 2 in formulas (A1-1) and (A1-2), and the structure represented by M
[0036] In formula (A1-3), L 3 represents a single bond or -O-, and L 4 represents a single bond, -O-, -COO-, -OCO-, -N=N-, -CH=CH- or -CH2-.
[0037] In formula (A1-3), R 6 and R 7 each independently represent a hydrogen atom, an alkyl group having 1 to 4 carbon atoms or an alkoxy group having 1 to 4 carbon atoms. Examples of the alkyl group represented by R 6 and R 7 include a methyl group, an ethyl group and a butyl group, and examples of the alkoxy group include a methoxy group, an ethoxy group and a butoxy group.
[0038] When the photo-aligning polymer (A) contains the structural unit (A1-1) or (A1-2) and the structural unit (A1-3), when the molar fractions of the structural unit (A1-1), (A1-2) and the structural unit (A1-3) with respect to all the structural units constituting the photo-aligning polymer (A) are p, q and r, respectively (where p + r = 1 and q + r = 1), it is preferable to satisfy the relationship of 0.10 < p, q ≤ 0.90 and 0.10 ≤ r < 0.90. In the photo-aligning polymer composed of the structural unit (A1-1), the structural unit (A1-1) may be one kind or two or more kinds. Further, the photo-aligning polymer (A) may have a structural unit other than the structural unit (A1-1), (A1-2) and the structural unit (A1-3) (hereinafter, also referred to as "other structural unit") as long as the liquid crystal aligning ability by light irradiation is not significantly impaired.
[0039] The photoalignable polymer (A) can be produced by (co)polymerizing a monomer that derives the structural unit (A1-1) or the structural unit (A1-2) and, if necessary, a monomer that derives the structural unit (A1-3) and / or other structural units. As the copolymerization method, a method conventionally known in the art may be adopted, for example, a chain polymerization such as radical polymerization, anionic polymerization, or cationic polymerization, and an addition polymerization method such as coordination polymerization. The polymerization conditions may be appropriately determined depending on the type and amount of the monomer used, so as to obtain a photoalignable polymer (A) having a desired molecular weight.
[0040] In the present invention, the molecular weight of the oriented polymer (A-1) is, in terms of polystyrene, a weight average molecular weight determined by gel permeation chromatography (GPC) measurement, preferably 10,000 to 1,000,000, more preferably 15,000 or more, even more preferably 20,000 or more, and more preferably 500,000 or less, even more preferably 250,000 or less. When the weight average molecular weight of the oriented polymer (A-1) is within the above range, the solvent resistance is good, and it is easy to obtain an oriented film that exhibits excellent liquid crystal aligning ability while ensuring high adhesion to a polarizing film that is later formed on the oriented film.
[0041] In the present invention, the oriented polymer (A-1) is preferably a photo-oriented polymer, more preferably a photo-oriented polymer (A), and even more preferably a (meth)acrylic polymer (particularly, a (meth)acrylic photo-oriented polymer (A)). In particular, when the polymerizable liquid crystal compound forming the polarizing film is a compound having a (meth)acryloyl group as a polymerizable group, if the oriented polymer (A-1) is a (meth)acrylic polymer, it is expected to have excellent affinity and further improve bending resistance that suppresses peeling between the polarizing film and the oriented film even when the bending diameter is small. In addition, in this specification, a polymer having the largest proportion of structural units based on a (meth)acrylic structure, such as (meth)acrylic acid ester units and (meth)acrylamide units, among all structural units constituting the polymer main chain, is collectively referred to as a "meth(acrylic) polymer".
[0042] The content of the oriented polymer (A-1) in the composition for forming an oriented film can be appropriately determined depending on the type of the oriented polymer used, the desired thickness of the oriented film, etc. The amount of the oriented polymer (A-1) used is not particularly limited as long as it is an amount that can completely dissolve the oriented polymer (A-1), but the content (concentration) is preferably 1.0 to 25.0 mass% and more preferably 2.5 to 22.5 mass% based on the total mass of the composition for forming an oriented film. In the composition for forming an oriented film, the oriented polymer (A-1) may be only one type or may be a combination of two or more types, but when two or more types are included, the total content thereof is preferably within the above range.
[0043] In the present invention, the composition for forming an alignment film contains an alignment polymer (A-1) and a compound (A-2) having an active hydrogen reactive group (hereinafter also referred to as "compound (A-2)"). In this specification, "active hydrogen reactive group" means a group that is reactive to a group having active hydrogen, such as a carboxyl group (-COOH), a hydroxyl group (-OH), an amino group (-NH2), or a mercapto group (-SH). When an alignment film is formed from a composition for forming an alignment film containing a compound (A-2) having an active hydrogen reactive group, it is easy to control the adhesion between the substrate and the alignment film, and the effect of suppressing peeling that may occur between the substrate and the alignment film when the obtained polarizing element is bent can be improved.
[0044] Examples of the active hydrogen reactive group that the compound (A-2) may have include an epoxy group, a glycidyl group, an oxazoline group, a carbodiimide group, an aziridine group, an imide group, an alkoxysilyl group, an isocyanate group, a thioisocyanate group, a maleic anhydride group, etc. Among these, from the viewpoint of adhesion, it is preferable that the compound (A-2) has at least one group selected from the group consisting of an alkoxysilyl group and an isocyanate group, and it is more preferable that the compound (A-2) has an alkoxysilyl group.
[0045] The number of active hydrogen reactive groups possessed by the compound (A-2) is at least 1. When a plurality of active hydrogen reactive groups are present, the plurality of active hydrogen reactive groups present may be the same or different.
[0046] It is preferable that the compound (A-2) further has an active hydrogen-containing group in addition to the active hydrogen-reactive group. In this specification, the "active hydrogen-containing group" means a functional group containing active hydrogen. When the compound (A-2) has an active hydrogen-containing group, it is easy to control the adhesion between the alignment film and the polarizing film, and the effect of suppressing peeling that may occur between the alignment film and the polarizing film when the obtained polarizing element is bent can be improved.
[0047] Examples of the active hydrogen-containing group that the compound (A-2) may have include a hydroxyl group, a carboxyl group, an amino group, a mercapto group, a primary amide group, a secondary amide group, a hydrazide group, etc. Among these, from the viewpoint of reactivity, adhesion, etc., it is preferable that the compound (A-2) has at least one group selected from the group consisting of a hydroxyl group, an amino group, and a mercapto group, and it is preferable that the compound (A-2) has an amino group or a mercapto group.
[0048] The number of active hydrogen-containing groups in the compound (A-2) is at least 1. When a plurality of active hydrogen-containing groups are present, the plurality of active hydrogen-containing groups may be the same or different.
[0049] In one embodiment of the present invention, the compound (A-2) is a silane coupling agent. When a silane coupling agent is used as the compound (A-2), it is easy to control the adhesion to the substrate or the polarizing film, and it is easy to obtain a polarizing element having excellent bending resistance. The silane coupling agent may be used alone or in combination of two or more.
[0050] As the silane coupling agent, compounds known in the art can be used.Specific examples of the silane coupling agent include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxysilane), 2-(1,2 ... Examples of suitable silanes include 3-(2-methyl-1,2-dimethylphenyl)ethyltrimethoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, 3-acryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropyldimethoxymethylsilane, and 3-glycidoxypropylethoxydimethylsilane.
[0051] The silane coupling agent may also be of silicone oligomer type. For example, the silicone oligomer type silane coupling agent may be, when the silicone oligomer is expressed in the form of (monomer) oligomer, a copolymer containing a mercaptopropyl group such as 3-mercaptopropyltrimethoxysilane-tetramethoxysilane copolymer, 3-mercaptopropyltriethoxysilane-tetramethoxysilane copolymer, 3-mercaptopropyltriethoxysilane-tetramethoxysilane copolymer, 3-mercaptopropyltriethoxysilane-tetraethoxysilane copolymer; mercaptomethyltrimethoxysilane-tetramethoxysilane copolymer, mercaptomethyltrimethoxysilane-tetraethoxysilane copolymer, mercaptomethyltriethoxysilane-tetramethoxysilane copolymer, mercaptomethyltriethoxysilane-tetramethoxysilane copolymer, mercaptomethyltriethoxysilane-tetraethoxy ..., mer copolymers containing mercaptomethyl groups; copolymers containing 3-glycidoxypropyl groups, such as 3-glycidoxypropyl trimethoxysilane-tetramethoxysilane copolymer, 3-glycidoxypropyl trimethoxysilane-tetraethoxysilane copolymer, 3-glycidoxypropyl triethoxysilane-tetramethoxysilane copolymer, 3-glycidoxypropyl triethoxysilane-tetraethoxysilane copolymer, 3-glycidoxypropyl methyl dimethoxysilane-tetramethoxysilane copolymer, 3-glycidoxypropyl methyl dimethoxysilane-tetraethoxysilane copolymer, 3-glycidoxypropyl methyl diethoxysilane-tetramethoxysilane copolymer, 3-glycidoxypropyl methyl diethoxysilane-tetramethoxysilane copolymer, and 3-glycidoxypropyl methyl diethoxysilane-tetraethoxysilane copolymer;3-methacryloyloxypropyltrimethoxysilane-tetramethoxysilane copolymer, 3-methacryloyloxypropyltrimethoxysilane-tetraethoxysilane copolymer, 3-methacryloyloxypropyltriethoxysilane-tetramethoxysilane copolymer, 3-methacryloyloxypropyltriethoxysilane-tetraethoxysilane copolymer, 3-methacryloyloxypropylmethyldimethoxysilane-tetramethoxysilane copolymer, 3-methacryloyloxypropylmethyldimethoxysilane-tetramethoxysilane copolymer, 3-methacryloyloxypropylmethyldimethoxysilane-tetraethoxysilane copolymer methacryloyloxypropyl group-containing copolymers such as 3-acryloyloxypropyltrimethoxysilane-tetramethoxysilane copolymer, 3-acryloyloxypropyltrimethoxysilane-tetraethoxysilane copolymer, 3-acryloyloxypropyltrimethoxysilane-tetraethoxysilane copolymer, 3-acryloyloxypropyltriethoxysilane-tetramethoxysilane copolymer, 3-acryloyloxypropyltriethoxysilane-tetramethoxysilane copolymer copolymers containing acryloyloxypropyl groups, such as 3-acryloyloxypropyltriethoxysilane-tetraethoxysilane copolymer, 3-acryloyloxypropylmethyldimethoxysilane-tetramethoxysilane copolymer, 3-acryloyloxypropylmethyldimethoxysilane-tetraethoxysilane copolymer, 3-acryloyloxypropylmethyldiethoxysilane-tetramethoxysilane copolymer, and 3-acryloyloxypropylmethyldiethoxysilane-tetraethoxysilane copolymer; vinyl group-containing copolymers such as silane-tetramethoxysilane copolymer, vinyltrimethoxysilane-tetraethoxysilane copolymer, vinyltriethoxysilane-tetramethoxysilane copolymer, vinyltriethoxysilane-tetraethoxysilane copolymer, vinylmethyldimethoxysilane-tetramethoxysilane copolymer, vinylmethyldimethoxysilane-tetraethoxysilane copolymer, vinylmethyldiethoxysilane-tetramethoxysilane copolymer, and vinylmethyldiethoxysilane-tetraethoxysilane copolymer;Examples of the copolymers include amino group-containing copolymers such as 3-aminopropyltrimethoxysilane-tetramethoxysilane copolymer, 3-aminopropyltrimethoxysilane-tetraethoxysilane copolymer, 3-aminopropyltriethoxysilane-tetramethoxysilane copolymer, 3-aminopropyltriethoxysilane-tetraethoxysilane copolymer, 3-aminopropylmethyldimethoxysilane-tetramethoxysilane copolymer, 3-aminopropylmethyldimethoxysilane-tetraethoxysilane copolymer, 3-aminopropylmethyldiethoxysilane-tetramethoxysilane copolymer, and 3-aminopropylmethyldiethoxysilane-tetraethoxysilane copolymer.
[0052] In one embodiment of the present invention, the silane coupling agent preferably has an active hydrogen-containing group. Specifically, it is more preferable that the silane coupling agent has at least one functional group selected from the group consisting of amino groups (primary and secondary), hydroxyl groups and mercapto groups, more preferably has a primary amino group or a secondary amino group, and is even more preferable that the silane coupling agent is a compound containing an Si element having the at least one functional group and at least one alkoxysilyl group or silanol group. The amino groups (primary and secondary), hydroxyl groups and mercapto groups have polarity, and by appropriately selecting these functional groups, the adhesion between the obtained alignment film and the polarizing film can be controlled, and the bending resistance of the polarizing element can be improved. From this viewpoint, it is preferable that the silane coupling agent is a silane coupling agent having an alkoxysilyl group and the at least one functional group. The functional group may have a suitable substituent or protective group to control the reactivity of the silane coupling agent. Examples of silane coupling agents having a protecting group include KBE-9103P (ketimine type) and X-12-1172ES (aldimine type) manufactured by Shin-Etsu Chemical Co., Ltd. as amino group protected types, and X-12-1056ES as mercapto group protected types.
[0053] A commercially available compound may be used as the compound (A-2). Examples of such commercially available products include KP321, KP323, KP324, KP326, KP340, KP341, X22-161A, KF6001, KBM-1003, KBE-1003, KBM-303, KBM-402, KBM-403, KBE-402, KBE-403, KBM-1403, KBM-502, KBM-503, KBE-502, KBE-503, KBM- Examples of silane coupling agents include those manufactured by Shin-Etsu Chemical Co., Ltd., such as silane coupling agents manufactured by Shin-Etsu Chemical Co., Ltd., such as KBM-5103, KBM-602, KBM-603, KBM-903, KBE-903, KBE-9103, KBM-573, KBM-575, KBM-9659, KBE-585, KBM-802, KBM-803, KBE-846, KBE-9007, X-12-1172ES, X-12-1154, and KR-519.
[0054] The content of the compound (A-2) in the composition for forming an alignment film can be appropriately determined depending on the type of the compound (A-2), the type and surface state of the substrate, the composition of the polarizing film, etc. In one embodiment of the present invention, the content of the compound (A-2) is preferably 1 part by mass or more and 30 parts by mass or less, more preferably 2.5 parts by mass or more and 25 parts by mass or less, even more preferably 5.0 parts by mass or more, and more preferably 23 parts by mass or less, relative to 100 parts by mass of the alignment polymer (A-1). When the content of the compound (A-2) is within the above range, it is easy to improve the bending resistance while maintaining good optical properties, and even when the bending diameter is small, the effect of suppressing peeling between the alignment film and the substrate and / or the polarizing film can be expected.
[0055] The composition for forming an alignment film usually contains a solvent. The solvent is not particularly limited as long as it can dissolve the components contained in the composition for forming a photoalignment film, and examples thereof include water; alcohol solvents such as methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, methyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, methyl amyl ketone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; aromatic hydrocarbon solvents such as toluene and xylene, nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; and chlorine-substituted hydrocarbon solvents such as chloroform and chlorobenzene. These solvents may be used alone or in combination of two or more.
[0056] In the present invention, the composition for forming an alignment film may contain any other components in addition to the above-mentioned components, as long as the properties of the alignment film are not significantly impaired. Examples of such components include polymer materials and photosensitizers.
[0057] The composition for forming an alignment film can be prepared, for example, by dissolving an alignment polymer (A-1) [or an oligomer or monomer capable of constituting the alignment polymer (A-1)] and a compound (A-2), and, if necessary, other components, in a solvent, and the composition for forming an alignment film can be cured, for example, according to a method described below, to obtain an alignment film, which is the cured product.
[0058] The thickness of the alignment film is usually in the range of 10 nm to 10,000 nm, preferably 10 nm to 2,500 nm, more preferably 10 nm to 1,000 nm, even more preferably 10 nm to 500 nm, and particularly preferably 20 nm to 250 nm. The thickness of the alignment film can be measured by a laser microscope, a film thickness meter, or the like, and the same applies to the measurement of the thickness of each layer such as the substrate and the polarizing film that constitute the polarizing element.
[0059] <Base material> The substrate constituting the polarizing element of the present invention can be a resin film or the like conventionally known in the field of optical films.The resin constituting the substrate can be, for example, a polyolefin resin such as polyethylene or polypropylene; a cyclic olefin resin such as norbornene polymer; a polyester resin such as polyethylene terephthalate or polyethylene naphthalate; a poly(meth)acrylic acid resin such as (meth)acrylic acid or poly(methyl meth)acrylate; a cellulose ester resin such as triacetyl cellulose, diacetyl cellulose and cellulose acetate propionate; a vinyl alcohol resin such as polyvinyl alcohol and polyvinyl acetate; a polycarbonate resin; a polystyrene resin; a polyarylate resin; a polysulfone resin; a polyethersulfone resin; a polyamide resin; a polyimide resin; a polyether ketone resin; a polyphenylene sulfide resin; a polyphenylene oxide resin, and mixtures thereof. Among these, from the viewpoints of improving flex resistance, versatility, heat resistance, and the like, at least one selected from the group consisting of vinyl alcohol-based resins, cellulose ester-based resins, cyclic olefin-based resins, and poly(meth)acrylic acid-based resins is preferred.
[0060] In the present invention, the substrate preferably has a polar group. Here, in this specification, the substrate having a polar group means that a polar group exists in the substrate before the alignment film is formed on the substrate. Examples of the polar group include a hydroxyl group, a carboxyl group, and an amino group. Among them, it is preferable to have at least one polar group selected from the group consisting of a hydroxyl group, a carboxyl group, and an amino group, from the viewpoint of being easily introduced to the substrate surface by a surface modification treatment of the substrate, and having good reactivity with the active hydrogen reactive group of the compound (A-2), as a material constituting the substrate, and more preferably having a hydroxyl group. By having the polar group in the substrate before the alignment film is formed, a bond derived from the reaction between the polar group present in the substrate and the active hydrogen reactive group of the compound (A-2) forming the alignment film is generated, and the adhesion between the substrate and the alignment film is increased, so that the obtained polarizing element can be given high bending resistance. Therefore, in one embodiment of the present invention, a bond (e.g., a Si-O bond) resulting from a reaction between a polar group (present on the substrate) and an active hydrogen reactive group (having compound (A-2)) may be present between the substrate and the alignment film constituting the polarizing element of the present invention.
[0061] The polar group is preferably present on the substrate surface on the side on which the alignment film is laminated. Such a substrate may be, for example, a substrate obtained by forming a film of a resin having a polar group, such as a vinyl alcohol resin or a cellulose resin, or a substrate obtained by forming a film (precursor film) from a material having a precursor group of a polar group, and then modifying the precursor group contained in the precursor film to a polar group. Examples of such a modification method include plasma treatment under vacuum or atmospheric pressure, corona treatment, laser treatment, ozone treatment, saponification treatment, or flame treatment. In addition, the substrate may be a substrate obtained by attaching a polymer having a polar group to the surface of a substrate made of a material having no polar group or its precursor group, or a substrate obtained by attaching a polymer having a precursor group of a polar group and then modifying the polymer to a polar group. Furthermore, the substrate may be a substrate obtained by attaching a monomer or polymer having a polar group to the surface of a substrate made of a material having no polar group or its precursor group, and then irradiating radiation, plasma, ultraviolet light, or the like to cause a reaction and graft polymerization. Examples of a method for attaching a polymer or monomer having a polar group or a precursor group of a polar group to the surface of a substrate include a method in which a solution in which the polymer or monomer is dissolved is applied to the surface of the substrate.
[0062] From the viewpoints of processability and thinning of the polarizing element, the thickness of the substrate is preferably from 1 μm to 20 μm, and more preferably from 1 μm to 10 μm.
[0063] <Polarizing film> In the present invention, the polarizing film is a film (layer) having a polarizing function. From the viewpoint of realizing an ultra-thin structure while ensuring bending resistance suitable for flexible display materials, the polarizing film in the polarizing element of the present invention is preferably a coating layer, and more preferably a polarizing film formed by curing a composition for forming a polarizing film, which contains a polymerizable liquid crystal compound (B-1), a compound (B-2) having an active hydrogen reactive group, and a dichroic dye (B-3).
[0064] The polymerizable liquid crystal compound (B-1) contained in the composition for forming a polarizing film is a compound having at least one polymerizable group. Here, the polymerizable group refers to a group that can participate in a polymerization reaction by an active radical or an acid generated from a polymerization initiator. Examples of the polymerizable group that the polymerizable liquid crystal compound (B-1) has include a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, a (meth)acryloyl group, an oxiranyl group, and an oxetanyl group. Among them, a radical polymerizable group is preferable, a (meth)acryloyl group, a vinyl group, and a vinyloxy group are more preferable, and a (meth)acryloyl group is even more preferable. When the polymerizable liquid crystal compound forming the polarizing film has the same functional group (polymerizable group) as the functional group of the compound forming the alignment film, such as a (meth)acryloyl group, the affinity between the alignment film and the polarizing film is increased, and the obtained polarizing element can be given excellent bending resistance.
[0065] In the present invention, the polymerizable liquid crystal compound (B-1) is preferably a liquid crystal compound exhibiting smectic liquid crystallinity. By using a polymerizable liquid crystal compound exhibiting smectic liquid crystallinity, a polarizing film having a high degree of alignment order can be formed. From the viewpoint of realizing a higher degree of alignment order, the liquid crystal state exhibited by the polymerizable liquid crystal compound (B-1) is more preferably a high-order smectic phase (high-order smectic liquid crystal state). Here, the high-order smectic phase means a smectic B phase, a smectic D phase, a smectic E phase, a smectic F phase, a smectic G phase, a smectic H phase, a smectic I phase, a smectic J phase, a smectic K phase, and a smectic L phase, and among these, the smectic B phase, the smectic F phase, and the smectic I phase are more preferable. The liquid crystallinity may be a thermotropic liquid crystal or a lyotropic liquid crystal, but a thermotropic liquid crystal is preferable in terms of enabling precise film thickness control. The polymerizable liquid crystal compound (B-1) may be a monomer, or may be an oligomer or polymer in which a polymerizable group is polymerized.
[0066] The polymerizable liquid crystal compound (B-1) is not particularly limited as long as it is a liquid crystal compound having at least one polymerizable group, and a known polymerizable liquid crystal compound can be used. For example, the polymerizable liquid crystal compound includes a compound represented by the following formula (B1) (hereinafter, sometimes referred to as "polymerizable liquid crystal compound (B1)"). U 1 -V 1 -W 1 -(X 1 -Y 1 ) n -X 2 -W 2 -V 2 -U 2 (B1) [In formula (B1), X 1 and X 2 represent, independently of each other, a divalent aromatic group or a divalent alicyclic hydrocarbon group, in which a hydrogen atom contained in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and a carbon atom constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with an oxygen atom, a sulfur atom, or a nitrogen atom. 1 and X 2 At least one of these is a 1,4-phenylene group which may have a substituent or a cyclohexane-1,4-diyl group which may have a substituent. Y 1 is a single bond or a divalent linking group. n is 1 to 3. If n is 2 or more, multiple X 1 may be the same or different. X 2 is multiple X 1 In addition, when n is 2 or more, a plurality of Y 1 may be the same as or different from each other. From the viewpoint of liquid crystallinity, n is preferably 2 or more. U 1 represents a hydrogen atom or a polymerizable group. U2 represents a polymerizable group. W 1 and W 2 are each independently a single bond or a divalent linking group. V 1 and V 2 each independently represents an alkanediyl group having 1 to 20 carbon atoms which may have a substituent, and -CH2- constituting the alkanediyl group may be replaced by -O-, -CO-, -S- or NH-.]
[0067] In the polymerizable liquid crystal compound (B1), X 1 and X 2 are each independently preferably an optionally substituted 1,4-phenylene group or an optionally substituted cyclohexane-1,4-diyl group; X 1 and X 2 At least one of the groups is a 1,4-phenylene group which may have a substituent, or a cyclohexane-1,4-diyl group which may have a substituent, and is preferably a trans-cyclohexane-1,4-diyl group. Examples of the optional substituent of the 1,4-phenylene group which may have a substituent, or the cyclohexane-1,4-diyl group which may have a substituent, include an alkyl group having 1 to 4 carbon atoms such as a methyl group, an ethyl group, and a butyl group, a cyano group, and a halogen atom such as a chlorine atom or a fluorine atom. It is preferably unsubstituted.
[0068] The polymerizable liquid crystal compound (B-1) is a compound represented by the formula (B1) having the formula (B1′): -(X 1 -Y 1 ) n -X 2 - (B1') [In the formula, X 1 , Y 1 , X 2 and n have the same meanings as above. [hereinafter, also referred to as partial structure (B1')] is preferably asymmetric in that smectic liquid crystal properties are easily exhibited. The polymerizable liquid crystal compound (B1) in which the partial structure (B1′) is an asymmetric structure is, for example, a compound in which n is 1 and one X 1 and X 2 and Y are different from each other. 1 A compound in which two Xs are the same structure. 1 are identical in structure to each other, and one X 2 These two X 1 A polymerizable liquid crystal compound (B1) having a structure different from that of the two X 1 Of the W 1 X binds to 1 But the other X 1 and X 2 The structure is different from that of the other X 1 and X 2 Further, the polymerizable liquid crystal compound (B1) may be a compound having the same structure as the compound (B1). 1 are the same structure as each other, and three X 1 and one X 2 The polymerizable liquid crystal compound (B1) includes any one of the following three structures different from all of the other three structures.
[0069] Y 1 are -CH2CH2-, -CH2O-, -CH2CH2O-, -COO-, -OCOO-, single bond, -N=N-, -CR a =CR b -, -C≡C-, -CR a =N- or -CO-NR a - is preferred. a and R b each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. 1 is more preferably -CH2CH2-, -COO- or a single bond, 1 If present, X 2 Y that binds to 1 is more preferably -CH2CH2- or CH2O-. 1 and X 2 When all of Y are the same structure, two or more Y1 It is preferable that there is a plurality of Y 1 When the compound has a structure of asymmetric structure, the compound tends to exhibit smectic liquid crystallinity.
[0070] U 2 is a polymerizable group. 1 is a hydrogen atom or a polymerizable group, and is preferably a polymerizable group. 1 and U 2 Preferably, both are polymerizable groups, and preferably both are radically polymerizable groups. Examples of the polymerizable group include the same groups as those exemplified above as the polymerizable group contained in the polymerizable liquid crystal compound (B-1). 1 and a polymerizable group represented by U 2 may be different from each other, but are preferably the same type of group; 1 and U 2 At least one of the groups is preferably a (meth)acryloyl group, and more preferably both of the groups are (meth)acryloyl groups. The polymerizable group may be in a polymerized state or an unpolymerized state, but is preferably in an unpolymerized state.
[0071] V 1 and V 2 Examples of the alkanediyl group represented by the formula (I) include a methylene group, an ethylene group, a propane-1,3-diyl group, a butane-1,3-diyl group, a butane-1,4-diyl group, a pentane-1,5-diyl group, a hexane-1,6-diyl group, a heptane-1,7-diyl group, an octane-1,8-diyl group, a decane-1,10-diyl group, a tetradecane-1,14-diyl group, and an icosane-1,20-diyl group. 1 and V 2 is preferably an alkanediyl group having 2 to 12 carbon atoms, and more preferably an alkanediyl group having 6 to 12 carbon atoms.
[0072] Examples of the substituent that the alkanediyl group may have include a cyano group and a halogen atom. The alkanediyl group is preferably unsubstituted, and more preferably an unsubstituted linear alkanediyl group.
[0073] W 1 and W 2 are each independently preferably a single bond, -O-, -S-, -COO- or -OCOO-, more preferably a single bond or -O-.
[0074] As a structure that is likely to exhibit smectic liquid crystal properties, it is preferable that the molecular structure has an asymmetric molecular structure, and the polymerizable liquid crystal compound (B-1) is more preferably a polymerizable liquid crystal compound that exhibits smectic liquid crystal properties, specifically, a polymerizable liquid crystal compound having the following partial structures (Ba) to (Bi). From the viewpoint of easily exhibiting high-order smectic liquid crystal properties, it is more preferable that the compound has the partial structure (Ba), (Bb) or (Bc). In the following (Ba) to (Bi), * represents a bond (single bond).
[0075] [ka]
[0076] Specific examples of the polymerizable liquid crystal compound (B-1) include compounds represented by formulae (B1-1) to (B1-25). When the polymerizable liquid crystal compound (B-1) has a cyclohexane-1,4-diyl group, the cyclohexane-1,4-diyl group is preferably a trans isomer.
[0077] [ka]
[0078] [ka]
[0079] [ka]
[0080] Among these, at least one selected from the group consisting of compounds represented by formula (B1-2), formula (B1-3), formula (B1-4), formula (B1-5), formula (B1-6), formula (B1-7), formula (B1-8), formula (B1-13), formula (B1-14), formula (B1-15), formula (B1-16) and formula (B1-17) is preferred. As the polymerizable liquid crystal compound (B-1), one type may be used alone, or two or more types may be used in combination.
[0081] The polymerizable liquid crystal compound (B-1) can be produced by a known method, for example, as described in Lub et al., Recl. Trav. Chim. Pays-Bas, 115, 321-328 (1996), or Japanese Patent No. 4,719,156.
[0082] In the present invention, the composition for forming a polarizing film may contain a polymerizable liquid crystal compound other than the polymerizable liquid crystal compound (B1). From the viewpoint of obtaining a polarizing film having a high degree of orientation order, the proportion of the polymerizable liquid crystal compound (B1) to the total mass of all the polymerizable liquid crystal compounds contained in the composition for forming a polarizing film is preferably 51 mass % or more, more preferably 70 mass % or more, and even more preferably 90 mass % or more.
[0083] When the composition for forming a polarizing film contains two or more polymerizable liquid crystal compounds, at least one of them may be the polymerizable liquid crystal compound (B1), or all of them may be the polymerizable liquid crystal compound (B1). By combining a plurality of polymerizable liquid crystal compounds, liquid crystallinity may be temporarily maintained even at a temperature below the liquid crystal-crystal phase transition temperature.
[0084] The content of the polymerizable liquid crystal compound (B-1) in the composition for forming a polarizing film is preferably 40 to 99.9% by mass, more preferably 60 to 99% by mass, and even more preferably 70 to 99% by mass, based on the solid content of the composition for forming a polarizing film. When the content of the polymerizable liquid crystal compound (B-1) is within the above range, the orientation of the polymerizable liquid crystal compound tends to be high. The solid content of the composition for forming a polarizing film refers to the total amount of components excluding volatile components such as solvents from the composition for forming a polarizing film, and hereinafter, when the term "solid content" is used in this specification, it similarly refers to the components excluding volatile components such as solvents from the target composition.
[0085] In the present invention, the composition for forming a polarizing film preferably contains a compound (B-2) (hereinafter also referred to as "compound (B-2)") having an active hydrogen reactive group. Examples of the active hydrogen reactive group possessed by the compound (B-2) include the same functional groups as those exemplified as the active hydrogen reactive group that may be possessed by the compound (A-2) contained in the composition for forming an alignment film. Among them, from the viewpoint of reactivity with the active hydrogen-containing group that may be possessed by the compound (A-2), it is preferable that the compound (B-2) has at least one group selected from the group consisting of an epoxy group, a glycidyl group, an isocyanate group, and an alkoxysilyl group, more preferably an isocyanate group or an alkoxysilyl group, and even more preferably an isocyanate group.
[0086] The number of active hydrogen reactive groups in the compound (B-2) is usually 1 to 20, preferably 1 to 10, and in a more preferred embodiment of the present invention, at least two active hydrogen reactive groups are present. When a plurality of active hydrogen reactive groups are present, the plurality of active hydrogen reactive groups present may be the same or different.
[0087] In addition to the active hydrogen reactive group, the compound (B-2) preferably further has a polymerizable group. The polymerizable group may be, for example, a carbon-carbon unsaturated bond such as a carbon-carbon double bond or a carbon-carbon triple bond, and specifically includes a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, a (meth)acryloyl group, an oxiranyl group, an oxetanyl group, and the like. Among them, in relation to the alignment polymer (A-1), when the compound (B-2) has the same functional group (polymerizable group) as the above compound, for example, a (meth)acryloyl group, the affinity between the alignment film and the polarizing film is increased, and the bending resistance of the obtained polarizing element can be further improved, so that a (meth)acryloyl group is preferred.
[0088] The compound (B-2) has usually 1 to 20 polymerizable groups, and preferably 1 to 10 polymerizable groups.
[0089] In one embodiment of the present invention, compound (B-2) preferably has, as an active hydrogen reactive group, at least one group selected from the group consisting of an epoxy group, a glycidyl group, an isocyanate group, and an alkoxysilyl group, and preferably contains, as a polymerizable group, a (meth)acryloyl group, and more preferably has one or more isocyanate groups and one or more (meth)acryloyl groups.
[0090] Specific examples of the compound (B-2) include compounds having a (meth)acrylic group and an epoxy group, such as methacryloyloxyglycidyl ether and acryloyloxyglycidyl ether; compounds having a (meth)acrylic group and an oxetanyl group, such as oxetane acrylate and oxetane methacrylate; compounds having a (meth)acrylic group and a lactone group, such as lactone acrylate and lactone methacrylate; compounds having a vinyl group and an oxazolyl group, such as vinyl oxazoline and isopropenyl oxazoline; compounds having a (meth)acrylic group and an isocyanate group, such as isocyanatomethyl acrylate, isocyanatomethyl methacrylate, 2-isocyanatoethyl acrylate and 2-isocyanatoethyl methacrylate; and oligomers of compounds having a (meth)acrylic group and an alkoxysilyl group, such as 3-acryloyloxypropyltrimethoxysilane and 3-methacryloyloxypropylmethyldimethoxysilane. Further, compounds having a vinyl group or vinylene group and an acid anhydride, such as methacrylic anhydride, acrylic anhydride, maleic anhydride, and vinyl maleic anhydride, can be mentioned. Among them, methacryloyloxyglycidyl ether, acryloyloxyglycidyl ether, isocyanatomethyl acrylate, isocyanatomethyl methacrylate, vinyloxazoline, 2-isocyanatoethyl acrylate, 2-isocyanatoethyl methacrylate, 3-acryloyloxypropyltrimethoxysilane, and the above oligomers are preferred, and isocyanatomethyl acrylate, 2-isocyanatoethyl acrylate, 3-acryloyloxypropyltrimethoxysilane, and the above oligomers are particularly preferred.
[0091] Compound (B-2) may be a commercially available product. Examples of such commercially available products include Laromer (registered trademark) PR9000 (manufactured by BASF), Karenz AOI (registered trademark) (manufactured by Showa Denko K.K.), Karenz BEI (registered trademark) (manufactured by Showa Denko K.K.), Karenz MOI-EG (registered trademark) (manufactured by Showa Denko K.K.), and KBM-5103 (manufactured by Shin-Etsu Chemical Co., Ltd.).
[0092] When the composition for forming a polarizing film contains a compound (B-2), the compound (B-2) may be the same as or different from the compound (A-2) contained in the composition for forming an alignment film.
[0093] The content of the compound (B-2) in the composition for forming a polarizing film is preferably 0.1 to 12 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 1 to 10 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound (B-1). When the content of the compound (B-2) is within the above range, the bending resistance of the polarizing element is easily improved without impairing the alignment of the obtained polarizing film. The compound (B-2) may be used alone or in combination of two or more kinds. When two or more kinds of the compound (B-2) are used, it is preferable that the total content thereof is within the above range.
[0094] In the present invention, the composition for forming a polarizing film usually contains a dichroic dye (B-3). Here, the dichroic dye means a dye having different properties between the absorbance in the long axis direction of the molecule and the absorbance in the short axis direction. The dichroic dye (B-3) that can be used in the present invention is not particularly limited as long as it has the above-mentioned properties, and may be a dye or a pigment. In addition, two or more kinds of dyes or pigments may be used in combination, or a dye and a pigment may be used in combination. In addition, the dichroic dye may have polymerizability or liquid crystal properties.
[0095] The dichroic dye (B-3) has a maximum absorption wavelength (λ ) in the range of 300 to 700 nm. MAX ) is preferable. Examples of such dichroic dyes include acridine dyes, oxazine dyes, cyanine dyes, naphthalene dyes, azo dyes, and anthraquinone dyes.
[0096] Examples of azo dyes include monoazo dyes, bisazo dyes, trisazo dyes, tetrakisazo dyes, and stilbene azo dyes. Bisazo dyes and trisazo dyes are preferred, and examples thereof include a compound represented by formula (I) (hereinafter also referred to as "compound (I)"). K 1 (-N=NK 2 ) p -N=NK 3 (I) [In formula (I), K 1 and K. 3 each independently represents a phenyl group which may be substituted, a naphthyl group which may be substituted, a phenyl benzoate group which may be substituted, or a monovalent heterocyclic group which may be substituted. 2 represents a p-phenylene group which may have a substituent, a naphthalene-1,4-diyl group which may have a substituent, a 4,4'-stilbenylene group which may have a substituent, or a divalent heterocyclic group which may have a substituent. p represents an integer of 0 to 4. When p is an integer of 2 or more, a plurality of K 2 may be the same or different. The -N=N- bond may be replaced with a -C=C-, -COO-, -NHCO-, or -N=CH- bond as long as the compound exhibits absorption in the visible region.
[0097] Examples of monovalent heterocyclic groups include groups in which one hydrogen atom has been removed from a heterocyclic compound such as quinoline, thiazole, benzothiazole, thienothiazole, imidazole, benzimidazole, oxazole, benzoxazole, etc. Examples of divalent heterocyclic groups include groups in which two hydrogen atoms have been removed from the above-mentioned heterocyclic compounds.
[0098] K 1 and K. 3 Phenyl, naphthyl, phenyl benzoate and monovalent heterocyclic groups in 2In the above formula, examples of the substituents that the p-phenylene group, the naphthalene-1,4-diyl group, the 4,4'-stilbenylene group, and the divalent heterocyclic group may optionally have include an alkyl group having 1 to 20 carbon atoms, an alkyl group having 1 to 20 carbon atoms and having a polymerizable group, an alkenyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, such as a methoxy group, an ethoxy group, or a butoxy group, an alkoxy group having 1 to 20 carbon atoms and having a polymerizable group, a fluorinated alkyl group having 1 to 4 carbon atoms, such as a trifluoromethyl group, Examples of the amino group include an ano group, a nitro group, a halogen atom, and a substituted or unsubstituted amino group such as an amino group, a diethylamino group, or a pyrrolidino group (the substituted amino group means an amino group having one or two alkyl groups having 1 to 6 carbon atoms, an amino group having one or two alkyl groups having 1 to 6 carbon atoms and a polymerizable group, or an amino group in which two substituted alkyl groups are bonded to each other to form an alkanediyl group having 2 to 8 carbon atoms. An unsubstituted amino group is -NH2). Examples of the polymerizable group include a (meth)acryloyl group and a (meth)acryloyloxy group.
[0099] Among the compounds (I), compounds represented by any one of the following formulas (I-1) to (I-8) are preferred. [ka] [In the formulas (I-1) to (I-8), B 1 ~B 30 each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, a nitro group, a substituted or unsubstituted amino group (the substituted amino group and the unsubstituted amino group are defined above), a chlorine atom, or a trifluoromethyl group. n1 to n4 each independently represent an integer of 0 to 3. If n1 is 2 or more, multiple B 2 may be the same or different, If n2 is 2 or more, multiple B 6 may be the same or different, If n3 is 2 or more, multiple B 9may be the same or different, If n4 is 2 or more, multiple B 14 may be the same or different.]
[0100] The anthraquinone dye is preferably a compound represented by formula (I-9). [ka] [In formula (I-9), R 1 ~R 8 are each independently a hydrogen atom, -R x , -NH2, -NHR x , -NR x 2, -SR x Or a halogen atom. R x represents an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms.
[0101] The oxazone dye is preferably a compound represented by formula (I-10). [ka] [In formula (I-10), R 9 ~R 15 are each independently a hydrogen atom, -R x , -NH2, -NHR x , -NR x 2, -SR x Or a halogen atom. R x represents an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms.
[0102] The acridine dye is preferably a compound represented by formula (I-11). [ka] [In formula (I-11), R 16 ~R 23are each independently a hydrogen atom, -R x , -NH2, -NHR x , -NR x 2, -SR x Or a halogen atom. R x represents an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms. In formula (I-9), formula (I-10) and formula (I-11), R x Examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, and a hexyl group, and examples of the aryl group having 6 to 12 carbon atoms include a phenyl group, a toluyl group, a xylyl group, and a naphthyl group.
[0103] As the cyanine dye, the compounds represented by formula (I-12) and formula (I-13) are preferred. [ka] [In formula (I-12), D 1 and D. 2 represent, independently of each other, a group represented by any one of formulae (I-12a) to (I-12d). [ka] n5 represents an integer from 1 to 3. [ka] [In formula (I-13), D 3 and D. 4 each independently represents a group represented by any one of formulas (I-13a) to (1-13h). [ka] n6 represents an integer from 1 to 3.
[0104] Among these dichroic dyes, azo dyes are suitable for producing a polarizing film having excellent polarizing performance because of their high linearity. Therefore, in one embodiment of the present invention, the dichroic dye (B-3) contained in the composition for forming a polarizing film that forms the polarizing film is preferably an azo dye.
[0105] In the present invention, the weight average molecular weight of the dichroic dye (B-3) is usually 300-2,000, and preferably 400-1,000.
[0106] In one embodiment of the present invention, the dichroic dye (B-3) contained in the composition for forming a polarizing film is preferably hydrophobic. When the dichroic dye (B-3) is hydrophobic, the compatibility between the dichroic dye (B-3) and the polymerizable liquid crystal compound (B-1) is improved, and the dichroic dye (B-3) and the polymerizable liquid crystal compound (B-1) form a uniform phase state, and a polarizing film having a high degree of orientation order can be obtained. In the present invention, the hydrophobic dichroic dye means a dye having a solubility of 1 g or less in 100 g of water at 25°C.
[0107] The content of the dichroic dye (B-3) in the composition for forming a polarizing film can be appropriately determined depending on the type of the dichroic dye used, and is preferably 0.1 to 50 parts by mass, more preferably 0.1 to 20 parts by mass, and even more preferably 0.1 to 12 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound. When the content of the dichroic dye (B-3) is within the above range, the orientation of the polymerizable liquid crystal compound is unlikely to be disturbed, and a polarizing film having a high degree of orientation order can be obtained.
[0108] In the present invention, the composition for forming a polarizing film for forming a polarizing film may contain a polymerization initiator. The polymerization initiator is a compound capable of initiating a polymerization reaction of the polymerizable liquid crystal compound (B-1), and a photopolymerization initiator is preferred in that the polymerization reaction can be initiated under lower temperature conditions. Specifically, a photopolymerization initiator capable of generating active radicals or acids by the action of light can be mentioned, and among these, a photopolymerization initiator that generates radicals by the action of light is preferred. The polymerization initiator can be used alone or in combination of two or more kinds.
[0109] As the photopolymerization initiator, a known photopolymerization initiator can be used. For example, photopolymerization initiators that generate active radicals include self-cleavage type photopolymerization initiators and hydrogen abstraction type photopolymerization initiators. Examples of the self-cleavage type photopolymerization initiator that can be used include self-cleavage type benzoin compounds, acetophenone compounds, hydroxyacetophenone compounds, α-aminoacetophenone compounds, oxime ester compounds, acylphosphine oxide compounds, azo compounds, etc. Examples of the hydrogen abstraction type photopolymerization initiator that can be used include hydrogen abstraction type benzophenone compounds, benzoin ether compounds, benzyl ketal compounds, dibenzosuberone compounds, anthraquinone compounds, xanthone compounds, thioxanthone compounds, halogenoacetophenone compounds, dialkoxyacetophenone compounds, halogenobisimidazole compounds, halogenotriazine compounds, triazine compounds, etc.
[0110] As the photopolymerization initiator that generates an acid, an iodonium salt, a sulfonium salt, or the like can be used.
[0111] Among these, reaction at low temperatures is preferred from the viewpoint of preventing dissolution of the dye, and self-cleavage type photopolymerization initiators are preferred from the viewpoint of reaction efficiency at low temperatures, with acetophenone-based compounds, hydroxyacetophenone-based compounds, α-aminoacetophenone-based compounds, and oxime ester-based compounds being particularly preferred.
[0112] Specific examples of the photopolymerization initiator include the following: Benzoin compounds such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether and benzoin isobutyl ether; Hydroxyacetophenone compounds such as 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1,2-diphenyl-2,2-dimethoxyethan-1-one, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]propan-1-one, 1-hydroxycyclohexyl phenyl ketone and oligomers of 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propan-1-one; α-aminoacetophenone compounds such as 2-methyl-2-morpholino-1-(4-methylthiophenyl)propan-1-one and 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one; Oxime ester compounds such as 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)], ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(O-acetyloxime); Acylphosphine oxide compounds such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide; Benzophenone compounds such as benzophenone, methyl o-benzoylbenzoate, 4-phenylbenzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone, and 2,4,6-trimethylbenzophenone; Dialkoxyacetophenone compounds such as diethoxyacetophenone; 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxynaphthyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxystyryl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(5-methylfuran-2-yl)ethenyl]-1,3,5-triazine triazine-based compounds such as riazine, 2,4-bis(trichloromethyl)-6-[2-(furan-2-yl)ethenyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(4-diethylamino-2-methylphenyl)ethenyl]-1,3,5-triazine, and 2,4-bis(trichloromethyl)-6-[2-(3,4-dimethoxyphenyl)ethenyl]-1,3,5-triazine. The photopolymerization initiator may be appropriately selected from the above photopolymerization initiators in consideration of the relationship with the polymerizable liquid crystal compound (B-1) and compound (B-2) contained in the composition for forming a polarizing film.
[0113] Commercially available photopolymerization initiators may also be used. Commercially available polymerization initiators include Irgacure (registered trademark) 907, 184, 651, 819, 250, and 369, 379, 127, 754, OXE01, OXE02, and OXE03 (manufactured by BASF); Omnirad BCIM, Esacure 1001M, and Esacure KIP160 (manufactured by IDM Resins); BV); Seikuol (registered trademark) BZ, Z, and BEE (manufactured by Seiko Chemical Co., Ltd.); Kayacure (registered trademark) BP100, and UVI-6992 (manufactured by The Dow Chemical Company); Adeka Optomer SP-152, N-1717, N-1919, SP-170, Adeka Arcles NCI-831, Adeka Arcles NCI-930 (manufactured by ADEKA Corporation); TAZ-A, and TAZ-PP (manufactured by Nippon SiberHegner Co., Ltd.); and TAZ-104 (manufactured by Sanwa Chemical Co., Ltd.).
[0114] The content of the polymerization initiator in the composition for forming a polarizing film for forming a polarizing film is preferably 1 to 10 parts by mass, more preferably 1 to 8 parts by mass, further preferably 2 to 8 parts by mass, and particularly preferably 4 to 8 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound (B-1). When the content of the polymerization initiator is within the above range, the polymerization reaction of the polymerizable liquid crystal compound can be carried out without significantly disturbing the alignment of the polymerizable liquid crystal compound.
[0115] The polarizing film forming composition may further contain a photosensitizer. The use of the photosensitizer can further promote the polymerization reaction of the polymerizable liquid crystal compound (B-1). Examples of the photosensitizer include xanthone compounds such as xanthone and thioxanthone (e.g., 2,4-diethylthioxanthone, 2-isopropylthioxanthone, etc.); anthracene compounds such as anthracene and an alkoxy group-containing anthracene (e.g., dibutoxyanthracene, etc.); phenothiazine, rubrene, etc. The photosensitizer can be used alone or in combination of two or more kinds.
[0116] When the composition for forming a polarizing film contains a photosensitizer, the content thereof may be appropriately determined depending on the types and amounts of the polymerization initiator and the polymerizable liquid crystal compound (B-1), and is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 0.5 to 8 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound (B-1).
[0117] The composition for forming a polarizing film may also contain a leveling agent. The leveling agent has the function of adjusting the fluidity of the composition for forming a polarizing film and making the coating film obtained by applying the composition for forming a polarizing film flatter, and specifically includes a surfactant. As the leveling agent, at least one selected from the group consisting of leveling agents mainly composed of a polyacrylate compound and leveling agents mainly composed of a fluorine atom-containing compound is preferable. The leveling agents can be used alone or in combination of two or more kinds.
[0118] Examples of leveling agents based on polyacrylate compounds include "BYK-350", "BYK-352", "BYK-353", "BYK-354", "BYK-355", "BYK-358N", "BYK-361N", "BYK-380", "BYK-381" and "BYK-392" (BYK Chemie).
[0119] Examples of leveling agents containing a fluorine atom-containing compound as a main component include "Megafac (registered trademark) R-08", "R-30", "R-90", "F-410", "F-411", "F-443", "F-445", "F-470", "F-471", "F-477", "F-479", "F-482" and "F-483" (DIC Corporation); "Surflon (registered trademark) S-381" and "S Examples of such products include "S-382", "S-383", "S-393", "SC-101", "SC-105", "KH-40" and "SA-100" (AGC Seimi Chemical Co., Ltd.); "E1830", "E5844" (Daikin Fine Chemical Research Institute, Ltd.); "F-TOP EF301", "F-TOP EF303", "F-TOP EF351" and "F-TOP EF352" (Mitsubishi Materials Electronic Chemicals Co., Ltd.).
[0120] When the composition for forming a polarizing film contains a leveling agent, the content thereof is preferably 0.05 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound (B-1). When the content of the leveling agent is within the above range, the polymerizable liquid crystal compound (B-1) is easily aligned, and unevenness is unlikely to occur, so that a smoother polarizing film tends to be obtained.
[0121] The polarizing film-forming composition may contain additives other than the photosensitizer and the leveling agent. Examples of the additives include antioxidants, release agents, stabilizers, colorants such as bluing agents, flame retardants, and lubricants. When the polarizing film-forming composition contains other additives, the content of the additives is preferably more than 0% and not more than 20% by mass, more preferably more than 0% and not more than 10% by mass, based on the solid content of the polarizing film-forming composition.
[0122] The composition for forming a polarizing film can be produced by a conventionally known method for preparing a composition for forming a polarizing film, and can be prepared, for example, by mixing and stirring the polymerizable liquid crystal compound (B-1), the compound (B-2) and the dichroic dye (B-3), and, if necessary, the polymerization initiator and the above-mentioned additives, etc. In addition, since compounds exhibiting smectic liquid crystallinity generally have high viscosity, from the viewpoint of improving the coatability of the composition for forming a polarizing film and facilitating the formation of a polarizing film, the viscosity may be adjusted by adding a solvent to the composition for forming a polarizing film.
[0123] The solvent used in the composition for forming a polarizing film can be appropriately selected depending on the solubility of the polymerizable liquid crystal compound (B-1), the compound (B-2) and the dichroic dye (B-3) used. Specifically, the same solvents as those exemplified above as solvents usable in the composition for forming an alignment film can be used. As the solvent, only one type may be used alone, or two or more types may be used in combination. The content of the solvent is preferably 100 to 1900 parts by mass, more preferably 150 to 900 parts by mass, and even more preferably 180 to 600 parts by mass, based on 100 parts by mass of the solid content of the composition for forming a polarizing film.
[0124] A polarizing film can be obtained by curing the composition for forming a polarizing film, for example, according to a method to be described later. For example, a polymerizable liquid crystal compound (B-1) such as the polymerizable liquid crystal compound (B1) can form a polarizing film by photopolymerization while maintaining a liquid crystal phase, particularly a smectic phase, preferably a high-order smectic phase. A polarizing film obtained by polymerization while maintaining a smectic phase has an advantage of high polarization performance, due to the action of the dichroic dye, compared to a conventional host-guest type polarizing film, that is, a polarizing film made of a nematic phase liquid crystal state. Furthermore, it has an advantage of excellent strength compared to a film coated with only a dichroic dye or a lyotropic liquid crystal.
[0125] In the present invention, the polarizing film is preferably a polarizer with a high degree of orientation order. A polarizer with a high degree of orientation order can obtain a Bragg peak derived from a higher-order structure such as a hexatic phase or a crystalline phase in X-ray diffraction measurement. The Bragg peak means a peak derived from a planar periodic structure of molecular orientation. Therefore, the polarizing film constituting the polarizing element of the present invention preferably exhibits a Bragg peak in X-ray diffraction measurement. That is, in the polarizing film constituting the polarizing element of the present invention, the polymerizable liquid crystal compound (B-1) or its polymer is preferably oriented so that the polarizing film exhibits a Bragg peak in X-ray diffraction measurement, and it is more preferable that the polymerizable liquid crystal compound (B-1) is "horizontally oriented" in which the molecules of the polymerizable liquid crystal compound (B-1) are oriented in the direction in which light is absorbed. In the present invention, a polarizer in which the planar periodicity of the molecular orientation is 3.0 to 6.0 Å is preferable. A high degree of orientation order that exhibits a Bragg peak can be realized by controlling the types and amounts of the polymerizable liquid crystal compound (B-1), compound (B-2) and dichroic dye (B-3) used, and the type and amount of the polymerization initiator.
[0126] The thickness of the polarizing film can be appropriately selected depending on the display device to which it is applied, and is preferably 0.1 to 10 μm, more preferably 0.3 to 9 μm, and further preferably 0.5 to 8 μm. When the film thickness of the polarizing film is equal to or more than the above lower limit, it is easy to prevent the necessary light absorption from becoming impossible, and when it is equal to or less than the above upper limit, it is easy to suppress the occurrence of alignment defects due to a decrease in the alignment regularity of the alignment film.
[0127] In one embodiment of the present invention, the polarizing element may include an overcoat layer on the surface of the polarizing film opposite to the alignment film. The overcoat layer may function, for example, to prevent the diffusion of the dichroic dye or to prevent damage to the polarizing film. The overcoat layer is not particularly limited as long as it can impart a desired function to the polarizing element, and examples of the overcoat layer include a layer formed from a resin composition containing a water-soluble polymer and a layer formed from a curable composition containing an active energy ray curable resin. Among them, the water-soluble polymer generally has a polarity significantly different from that of the dichroic dye, and therefore has an excellent effect of preventing the diffusion of the dichroic dye, and can be expected to improve the flex resistance by forming a bond with the active hydrogen reactive group of the compound (B-2) contained in the composition for forming a polarizing film. Therefore, in one embodiment of the present invention, the overcoat layer is preferably a layer formed from a resin composition containing a water-soluble polymer.
[0128] Examples of water-soluble polymers that can form the overcoat layer include polyacrylamide-based polymers, polyvinyl alcohol, vinyl alcohol-based polymers such as ethylene-vinyl alcohol copolymers, (meth)acrylic acid or its anhydride-vinyl alcohol copolymers, carboxyvinyl-based polymers, polyvinylpyrrolidone, starches, sodium alginate, and polyethylene oxide-based polymers. These polymers may be used alone or in combination of two or more.
[0129] When the overcoat layer is a layer formed from a resin composition containing a water-soluble polymer (hereinafter also referred to as a "water-soluble polymer-containing resin composition"), the content of the water-soluble polymer in the layer is preferably 75 mass % or more, more preferably 80 mass % or more, and even more preferably 85 mass % or more.
[0130] When the overcoat layer is a layer formed from a water-soluble polymer-containing resin composition, a crosslinking structure may be introduced by using a crosslinking agent to increase the density of the layer. Examples of such crosslinking agents include water-soluble additives and crosslinking agents such as ionic crosslinking agents such as glyoxylate salts and epoxy crosslinking agents, as well as hydrophobic crosslinking agents such as isocyanate crosslinking agents, polyaldehyde crosslinking agents such as glyoxal and glyoxal derivatives, and metal compound crosslinking agents such as zirconium chloride or titanium lactate for the purpose of imparting water resistance.
[0131] When a crosslinking agent is used, the amount of the crosslinking agent added may be appropriately determined depending on the type of the crosslinking agent used, etc. For example, the amount may be 0.1 to 100 parts by mass, preferably 1 to 50 parts by mass, and more preferably 10 to 30 parts by mass, relative to 100 parts by mass of the water-soluble polymer. When the content of the crosslinking agent is within the above range, the overcoat layer becomes dense, and the shielding effect against the dichroic dye (B-3) in the polarizing film is likely to be improved.
[0132] The water-soluble polymer-containing resin composition capable of forming the overcoat layer is usually prepared as a solution in which the water-soluble polymer is dissolved in a solvent. The solvent may be selected depending on the water-soluble polymer to be used, but typically includes water, alcohol, a mixture of water and alcohol, etc., and water is preferred.
[0133] The solid content concentration of the water-soluble polymer-containing resin composition obtained by adding a solvent to the components constituting the overcoat layer, such as the water-soluble polymer and the crosslinking agent, is preferably 1 to 50 mass%, more preferably 2 to 30 mass%, and further preferably 3 to 15 mass%. When the solid content concentration of the water-soluble polymer-containing resin composition is within the above range, the viscosity of the composition is low, and therefore the coatability and handleability are improved.
[0134] The water-soluble polymer-containing resin composition may contain other components such as additives in addition to the water-soluble polymer, the crosslinking agent, and the solvent such as water. Examples of such other components include preservatives and leveling agents. When the water-soluble polymer-containing resin composition contains other components such as additives, the amount of such components is preferably 10% by mass or less, more preferably 5% by mass or less, based on the solid content of the resin composition.
[0135] The overcoat layer can be formed by dissolving necessary components such as a water-soluble polymer and a crosslinking agent in a solvent to prepare a water-soluble polymer-containing resin composition, and curing the composition according to a method to be described later, for example.
[0136] The thickness of the overcoat layer can be appropriately selected depending on the material constituting the overcoat layer and the display device it is used in. The thickness of the overcoat layer may be, for example, 0.1 to 5.0 μm, and preferably 0.5 to 3.0 μm.
[0137] The polarizing element of the present invention may, for example, be (1) a step of forming a coating film of an alignment film-forming composition containing an alignment polymer (A-1) and a compound (A-2) having an active hydrogen reactive group on a substrate having a polar group, and drying the coating film to react the active hydrogen reactive group of the compound (A-2) with the polar group of the substrate to form a bond; (2) forming an alignment layer by subjecting the dried coating film obtained in step (1) to a rubbing treatment or light irradiation; (3) forming a coating film of a polarizing film-forming composition containing a polymerizable liquid crystal compound (B-1), a compound having an active hydrogen reactive group (B-2), and a dichroic dye (B-3) on the alignment film obtained in the step (2), and drying the coating film; and (4) A step of curing the polymerizable liquid crystal compound (B-1) and the dichroic dye (B-3) in the dried coating film obtained in step (3) in an aligned state to form a polarizing film. Hereinafter, this production method is also referred to as "the method for producing a polarizing element of the present invention".
[0138] In step (1), the method for applying the composition for forming an alignment film to the substrate may be a known method, such as a coating method including a spin coating method, an extrusion method, a gravure coating method, a die coating method, a bar coating method, and an applicator method, or a printing method including a flexography method.
[0139] The solvent in the coating film of the obtained composition for forming an alignment film is dried, and the active hydrogen reactive group of the compound (A-2) and the polar group of the substrate are reacted to form bonds derived from these functional groups. This can ensure higher adhesion between the substrate and the alignment film. Drying methods for removing the solvent contained in the coating film of the composition for forming an alignment film include natural drying, ventilation drying, heat drying, and reduced pressure drying. Among them, heat drying is preferred from the viewpoint of promoting the reaction between the active hydrogen reactive group of the compound (A-2) and the polar group of the substrate and from the viewpoint of productivity. The conditions for heat drying may be appropriately determined depending on the composition of the composition for forming an alignment film, the type of substrate, the thickness of the alignment film, and the like. For example, the heating temperature may be 50 to 200°C, and preferably 100 to 150°C. The drying time is usually 20 seconds to 10 minutes, and preferably 30 seconds to 5 minutes.
[0140] When the alignment film is a rubbed alignment film, the rubbed alignment film is obtained by subjecting the dried coating film of the composition for forming an alignment film obtained in step (1) to a rubbing treatment in step (2). As a rubbing treatment method, for example, a method of contacting the dried coating film of the composition for forming an alignment film obtained in step (1) with a rotating rubbing roll around which a rubbing cloth is wound can be mentioned.
[0141] When the alignment film is a photo-alignment film, the dried coating film of the composition for forming an alignment film obtained in step (1) is irradiated with light in step (2) to obtain a photo-alignment film. The direction of the alignment regulating force can be arbitrarily controlled by selecting the polarization direction of the polarized light to be irradiated.
[0142] The polarized light irradiation method may be a method of directly irradiating the dried coating film of the composition for forming an alignment film formed on a substrate with polarized light, or a method of irradiating the polarized light from the substrate side and transmitting the polarized light. The polarized light is preferably substantially parallel light. The wavelength of the polarized light to be irradiated is preferably in a wavelength range in which the photoreactive group of the photoalignable polymer can absorb light energy. Specifically, UV (ultraviolet light) having a wavelength of 250 to 400 nm is preferable. Examples of light sources used for the polarized light irradiation include xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, ultraviolet lasers such as KrF and ArF, and high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps are more preferable. These lamps are preferable because they have a high emission intensity of ultraviolet light with a wavelength of 313 nm. The light from the light source can be irradiated through an appropriate polarizer to irradiate the polarized light. As such a polarizer, a polarizing filter, a polarizing prism such as Glan-Thompson or Glan-Taylor, or a wire grid type polarizer can be used.
[0143] If masking is performed during the rubbing treatment or the irradiation of polarized light, a plurality of regions (patterns) in which the liquid crystal alignment directions are different can be formed.
[0144] In step (3), the method of applying the composition for forming a polarizing film on the alignment film may be the same as the method of applying the composition for forming an alignment film on a substrate. The obtained coating film of the composition for forming a polarizing film is dried or the like to remove the solvent under conditions in which the polymerizable liquid crystal compound (B-1) contained in the coating film does not polymerize, to form a dried coating film. The drying method may be the same as the method of drying the coating film of the composition for forming an alignment film. In addition, when the compound (A-2) in the composition for forming an alignment film is a compound having an active hydrogen-containing group, the solvent in the coating film of the composition for forming a polarizing film may be dried, and the active hydrogen-containing group of the compound (A-2) and the active hydrogen-reactive group of the compound (B-2) may be reacted to form bonds derived from these functional groups. This can ensure higher adhesion between the alignment film and the polarizing film.
[0145] Furthermore, in order to cause the polymerizable liquid crystal compound (B-1) to undergo a phase transition to a liquid phase, the temperature is raised to a temperature at which the polymerizable liquid crystal compound (B-1) undergoes a phase transition to a liquid phase or higher, and then the temperature is lowered to cause the polymerizable liquid crystal compound (B-1) to undergo a phase transition to a liquid crystal phase (smectic phase). Such a phase transition may be performed after the removal of the solvent in the coating film in step (3) or simultaneously with the removal of the solvent.
[0146] In step (4), the polymerizable liquid crystal compound (B-1) is polymerized while maintaining the liquid crystal state of the polymerizable liquid crystal compound (B-1), thereby forming a polarizing film as a cured product of the composition for forming a polarizing film. The polymerization method is preferably a photopolymerization method. In the photopolymerization, the light to be irradiated to the dried coating film is appropriately selected depending on the type of the polymerizable liquid crystal compound (B-1) contained in the dried coating film (particularly the type of polymerizable group possessed by the polymerizable liquid crystal compound (B-1)), the type of polymerization initiator and the amount thereof, etc. Examples of the light source include the same as those exemplified in the formation of the photoalignment film. The irradiation energy is 10 to 5000 mJ / cm2 of irradiation intensity in a wavelength region effective for activating the polymerization initiator. 2 It is preferable to set the value so as to be within a range of 100 to 2000 mJ / cm. 2It is preferable to select the type of polymerizable liquid crystal compound (B-1) and polymerization initiator constituting the composition for forming a polarizing film so that the composition can be photopolymerized by ultraviolet light. In addition, the polymerization temperature can be controlled by irradiating the dried coating film with light while cooling it with an appropriate cooling means during polymerization. A patterned polarizing film can also be obtained by performing masking and development during photopolymerization.
[0147] Furthermore, the method for producing a polarizing element of the present invention may further include a step of forming an overcoat layer on the polarizing film formed in step (4).
[0148] For example, when the overcoat layer is formed from a water-soluble polymer-containing resin composition, the water-soluble polymer-containing resin composition can be applied to the surface of the polarizing film opposite the alignment film, and the solvent in the coating can be dried and removed, followed by curing to obtain the overcoat layer.
[0149] The method for applying the water-soluble polymer-containing resin composition is not particularly limited, and may be the same as the method for applying the composition for forming an alignment film.
[0150] The drying temperature and time for forming an overcoat layer from a coating film of the water-soluble polymer-containing resin composition are not particularly limited, and may be appropriately determined depending on the composition of the water-soluble polymer-containing resin composition used. The drying treatment can be carried out, for example, by blowing hot air, and the temperature is usually within a range of 40 to 100° C., preferably 60 to 100° C. The drying time is usually 10 to 600 seconds.
[0151] The polarizing element of the present invention has a configuration that realizes high bending resistance while easily adapting to ultra-thinning. For example, when the polarizing element is composed of a substrate, an alignment film, and a polarizing film, the total thickness can be made 1.0 to 10.0 μm.
[0152] The polarizing element of the present invention can be used in a variety of display devices. The display device is a device having a display element, and includes a light-emitting element or a light-emitting device as a light source. Examples of the display device include a liquid crystal display device, an organic electroluminescence (EL) display device, an inorganic electroluminescence (EL) display device, a touch panel display device, an electron emission display device (e.g., a field emission display device (FED) and a surface field emission display device (SED)), an electronic paper (a display device using electronic ink or an electrophoretic element, a plasma display device, a projection display device (e.g., a grating light valve (GLV) display device, a display device having a digital micromirror device (DMD)), and a piezoelectric ceramic display. The liquid crystal display device includes any of a transmissive liquid crystal display device, a semi-transmissive liquid crystal display device, a reflective liquid crystal display device, a direct-view liquid crystal display device, and a projection liquid crystal display device. These display devices may be display devices that display two-dimensional images, or stereoscopic display devices that display three-dimensional images. In particular, the polarizing element of the present invention can be suitably used in an organic electroluminescence (EL) display device and an inorganic electroluminescence (EL) display device, and can also be suitably used in a liquid crystal display device and a touch panel display device.
[0153] In addition, the polarizing element of the present invention can be suitably used in flat panel displays, and is also suitable as a flexible display material because it has high bending resistance and can be made ultra-thin. The flexible display material of the present invention can be suitably incorporated into flexible image displays. EXAMPLES
[0154] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In the examples, "%" and "parts" mean mass% and mass parts, respectively, unless otherwise specified.
[0155] 1. Example 1 (1) Preparation of composition for forming photoalignment film Synthesis Example 1: Synthesis of Oriented Polymer 1 The oriented polymer 1 is composed of the following structural units: [Oriented polymer 1] [ka]
[0156] [Synthesis scheme of oriented polymer 1] [ka]
[0157] [Synthesis of compound (a1-1-1)] 50 g (258 mmol) of ferulic acid was dissolved in 360 g of methanol. 10 g of sulfuric acid was added to the obtained solution at room temperature, and the temperature was raised until the solvent refluxed, and the mixture was reacted under reflux for 2 hours. After cooling the obtained reaction solution, 150 g of ice and 150 g of water were added. The supernatant was removed by decantation, and 150 g of water at 5°C was added to crystallize the mixture. The obtained white crystals were filtered. The filtered white crystals were further washed with 1 M aqueous sodium bicarbonate solution and water, and then dried in vacuum to obtain 22.2 g of compound (a1-1-1). The yield was 83% based on ferulic acid.
[0158] [Synthesis of compound (b1-1-1)] 25 g (120 mmol) of compound (a1-1-1) was dissolved in 250 g of dimethylacetamide. 33.19 g (240 mmol) of potassium carbonate and 1.99 g (12 mmol) of potassium iodide were added to the obtained solution. 6-chlorohexanol was added dropwise to the obtained dispersion, and the mixture was stirred at room temperature for 1 hour, and then stirred at 70°C for 8 hours. The obtained reaction solution was filtered to remove insoluble matter. 200 g of methyl isobutyl ketone and 300 g of water were added to the filtrate, and the mixture was stirred, allowed to stand, and separated to recover the organic layer. 200 g of water was added to the recovered organic layer, and a series of water washing operations of stirring, allowing to stand, and separating was repeated twice. The solvent was removed from the recovered organic layer by reduced pressure distillation using an evaporator to obtain a crude product of compound (b1-1-1).
[0159] [Synthesis of compound (c1-1-1)] The entire amount of the crude product of the compound (b1-1-1) was dissolved in 185 g of ethanol. 92 g of water and 14.41 g (360 mmol) of sodium hydroxide were added to the obtained solution and stirred at 80° C. for 1 hour. After cooling the reaction solution to about 3° C., 2 M aqueous hydrochloric acid was added while keeping the temperature below 5° C. to adjust the pH to 2. The acidified white precipitate was filtered, washed twice with a mixed solution of 100 g of water and 80 g of methanol, and then dried in vacuum to obtain 30.4 g of compound (c1-1-1). The yield was 86% based on compound (a1-1-1).
[0160] [Synthesis of compound (M1-1-1)] 27.46g (93mmol) of compound (c1-1-1) was dissolved in 280g of chloroform. 2.06g of BHT (di-t-butyl-hydroxytoluene) and 37.73g (373mmol) of triethylamine were added to the obtained solution as a polymerization inhibitor and stirred under ice cooling. 29.26g (260mmol) of methacrylic acid chloride was added dropwise to the reaction solution, and the mixture was stirred for 5 hours while maintaining the temperature below 5°C. 5.7g of dimethylaminopyridine and 190g of water were added to the obtained reaction solution, and the mixture was stirred at room temperature for 12 hours. After standing, the organic layer was collected, and 100g of 2N aqueous hydrochloric acid was added to the organic layer, and a series of washing operations of stirring, standing and separation was repeated twice. The organic layer was collected, and 300g of n-heptane was added, and the precipitated crystals were collected by filtration. The precipitate was washed twice with a mixed solvent of 100 g of water and 80 g of methanol, and then dried in a vacuum to obtain 22.0 g of compound (M1-1-1). The yield was 65% based on compound (c1-1-1).
[0161] [Synthesis of Oriented Polymer 1] In a Schlenk flask, 1.00 g (2.76 mmol) of compound (M1-1-1) and 10 g of tetrahydrofuran were added, and after deoxygenation, 2.27 mg of azobisisobutyronitrile (AIBN) was added while flowing nitrogen, and the mixture was stirred at 60° C. for 72 hours. The resulting reaction solution was added to 200 g of toluene. The precipitate was collected by filtration, washed with heptane, and then vacuum dried to obtain 0.75 g of oriented polymer 1. The yield was 75% based on compound (M1-1-1). From GPC measurement, the molecular weight of the obtained oriented polymer 1 was a number average molecular weight of 28200, a weight average molecular weight of about 51300, Mw / Mn of 1.82, and the monomer content was 0.5%.
[0162] Synthesis Examples 2 and 3: Synthesis of Oriented Polymer 2 and Oriented Polymer 3 Oriented polymer 2 and oriented polymer 3 having the following structures were synthesized by the method described in Macromolecules, Vol. 39, No. 26, 9357 (2006). The numbers in parentheses in the following structural formulas represent the molar fraction of each structural unit relative to the total structural units of oriented polymer 2 and oriented polymer 3. [ka]
[0163] [ka]
[0164] The weight average molecular weight of oriented polymer 2 is about 100,000, and the weight average molecular weight of oriented polymer 3 is about 90,000.
[0165] Synthesis Example 4: Synthesis of Oriented Polymer 4 Oriented polymer 4 having the following structure was synthesized according to the synthesis method of the above-mentioned oriented polymer 2 and oriented polymer 3. The numbers in parentheses in the following structural formula represent the molar fraction of each structural unit relative to the total structural units of oriented polymer 4. [ka]
[0166] The weight average molecular weight of the oriented polymer 4 is about 95,000.
[0167] Preparation of composition for forming photo-alignment film 2 parts of the oriented polymer (oriented polymer 1) prepared above was mixed with 98 parts of o-xylene, and the mixture was stirred at 80° C. for 1 hour to obtain oriented polymer solution 1. Next, 1.0 part of 3-aminopropyltriethoxysilane (trade name: KBE-903, manufactured by Shin-Etsu Chemical Co., Ltd.) as compound (A-2) was added to the obtained oriented polymer solution 1 relative to 100 parts of the oriented polymer, and mixed to obtain a composition for forming a photo-oriented film.
[0168] (2) Preparation of composition for forming polarizing film A composition for forming a polarizing film was obtained by mixing the following components and stirring at 80° C. for 1 hour. The polymerizable liquid crystal compound and the dichroic dye used were the polymerizable liquid crystal compound and the azo dye described in the examples of JP2013-101328A. 75 parts of a polymerizable liquid crystal compound represented by formula (A-6) [ka] 25 parts of a polymerizable liquid crystal compound represented by formula (A-7) [ka] 2.8 parts of the dichroic dye (1) shown below [ka] 2.8 parts of the dichroic dye (2) shown below [ka] 2.8 parts of the dichroic dye (3) shown below [ka] Polymerization initiator: 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one (Irgacure 369; manufactured by Ciba Specialty Chemicals) 6 parts Leveling agent: Polyacrylate compound (BYK-361N; manufactured by BYK-Chemie) 1.2 parts Compound (B-2): 2 parts of a compound having the following structure (product name: Laromer (registered trademark) LR-9000, manufactured by BASF) [ka] Solvent: Cyclopentanone 250 parts
[0169] (3) Preparation of acrylic resin film An acrylic resin film was produced based on the description in JP 2020-56835 A. A composition for forming an acrylic resin layer was obtained by mixing 90 parts of a multifunctional acrylate monomer (ethylene oxide (12 units) dipentaerythritol hexaacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd., "NK Ester A-DPH-12E"), 10 parts of a urethane acrylate polymer (urethane acrylate (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., "Shikou UV-3310B"), 3 parts of a radical polymerization initiator (phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (manufactured by BASF, "Irgacure 819")), and 10 parts of a solvent (methyl ethyl ketone) and stirring at 50°C for 4 hours. The release-treated surface of a release-treated polyethylene terephthalate film (SP-PLR382050 manufactured by Lintec Corporation) (release film) was subjected to a corona treatment, and then the above-mentioned acrylic resin layer-forming composition was applied by a bar coating method (#2 30 mm / s), and the exposure dose was 500 mJ / cm using a UV irradiation device (SPOT CURE SP-7; manufactured by Ushio Inc.). 2 The coating layer of the resin layer-forming composition was irradiated with ultraviolet light of wavelength 365 nm to obtain an acrylic resin film having an acrylic resin layer formed on the surface of the release film. The thickness of the acrylic resin layer was 1.5 μm.
[0170] (4) Preparation of polarizing elements The acrylic resin film prepared above was cut into a square (10 cm long x 10 cm wide) as a substrate, and in order to introduce polar groups onto the substrate surface, it was treated once using a corona treatment device (AGF-B10; manufactured by Kasuga Electric Co., Ltd.) under conditions of an output of 0.3 kW and a treatment speed of 3 m / min. The corona-treated surface was coated with the composition for forming a photoalignment film using a bar coater, dried at 80°C for 1 minute, and irradiated with 100 mJ / cm using a polarized UV irradiation device (SPOT CURE SP-7 with polarizer unit; manufactured by Ushio Inc.). 2 A photo-alignment film was formed by exposing the film to polarized UV light with an integrated light amount of 40 nm. The thickness of the photo-alignment film was measured with an ellipsometer M-220 (manufactured by JASCO Corporation) and found to be 40 nm.
[0171] A composition for forming a polarizing film was applied onto the obtained photo-alignment film using a bar coater, and then dried in a drying oven set at 120° C. for 1 minute.
[0172] Thereafter, ultraviolet light was irradiated using a high-pressure mercury lamp (Uniquer VB-15201BY-A, manufactured by Ushio Electric Co., Ltd.) (under a nitrogen atmosphere, wavelength: 365 nm, cumulative light intensity at wavelength 365 nm: 1000 mJ / cm 2 ) to form a polarizing film in which the polymerizable liquid crystal compound and the dichroic dye were aligned, and a polarizing element (1) consisting of a substrate / photo-alignment film / polarizing film was obtained. At this time, the thickness of the polarizing film was measured by an ellipsometer and found to be 2.0 μm.
[0173] (5) Characterization [Adhesion evaluation] The adhesion between the photoalignment film and the substrate in the obtained polarizing element (1) was evaluated by the following method.
[0174] (Cross-hatch test) The adhesion between the photo-alignment film and the substrate in the obtained polarizing element (1) was evaluated by a cross-hatch test in accordance with JIS D0202-1988 (JIS "checkerboard adhesion test"). On the substrate side surface of a 10 cm x 10 cm polarizing element, scratches were made in a 10 x 10 checkerboard pattern at 2 mm intervals that penetrated through to the substrate and the photo-alignment film to create a checkerboard pattern. An adhesive tape (25 mm wide, made by Nichiban) was completely attached to the checkerboard surface. The adhesive tape was then peeled off in a direction 90° to the surface.
[0175] The number of squares that remained unpeeled was counted to evaluate adhesion. For the peeled squares, X-ray photoelectron spectroscopy (XPS) was used to confirm that the peeled interface was between the photo-alignment film and the substrate. The results are shown in Table 1.
[0176] [Optical property evaluation (measurement of polarization degree Py and single unit transmittance Ty)] The polarization degree Py and the single transmittance Ty of the polarizing element were measured as follows. The transmittance (Ta) in the transmission axis direction and the transmittance (Tb) in the absorption axis direction in the wavelength range of 380 nm to 780 nm were measured by the double beam method using a device in which a folder with a polarizer was set on a spectrophotometer (UV-3150 manufactured by Shimadzu Corporation). The reference side of the folder was provided with a mesh that cuts the amount of light by 50%. The single transmittance and the polarization degree at each wavelength were calculated using the following formulas (Formula 1) and (Formula 2), and further, luminosity correction was performed using a 2-degree visual field (C light source) of JIS Z 8701 to calculate the luminosity-corrected single transmittance (Ty) and luminosity-corrected polarization degree (Py). The results are shown in Table 1. Single transmittance Ty(%)=(Ta+Tb) / 2 (Equation 1) Degree of polarization Py(%) = (Ta-Tb) / (Ta+Tb)×100 (Equation 2)
[0177] [Evaluation of bending resistance] The evaluation of flex resistance was carried out as follows using the method of General Test Method for Paints - Flex Resistance (Cylindrical Mandrel Method) described in JIS-K-5600-5-1. The polarizing element (1) was cut into a 25 mm x 200 mm square. Using a cylindrical mandrel method bending resistance tester type II (manufactured by TP Giken Co., Ltd.), the cut polarizing element (1) was wrapped around a mandrel rod with a diameter of 2 mm (bending radius R = 1 mm) with the polarizing film surface facing outward under conditions of 25 ° C. and 55% RH relative humidity, and a bending resistance test was performed. The polarizing element (1) after the test was visually confirmed in a darkroom environment with transmitted light from an illumination, and the occurrence of peeling between the substrate and the alignment film was observed. Complete peeling was judged as "x", partial peeling was judged as "△", and no peeling was judged as "○". The results are shown in Table 1.
[0178] 2. Examples 2 to 23 and Comparative Example 1 A polarizing element was produced and evaluated in the same manner as in Example 1, except that the types and amounts of the orienting polymer (A-1), compound (A-2) and compound (B-2) were changed according to the composition shown in Table 1. The results obtained are shown in Table 1.
[0179] In Examples 13 to 18, the following compound (A-2) and compound (B-2) were used. <Compound (A-2)> X-12-1172ES (Shin-Etsu Chemical Co., Ltd.): [ka] X-12-1154 (Shin-Etsu Chemical Co., Ltd.): Organic chain type, containing mercapto group KR-519 (Shin-Etsu Chemical Co., Ltd.): Silicone oligomer, containing mercapto groups <Compound (B-2)> Karenz A01 (Showa Denko Co., Ltd.): [ka] Karenz BEI (Showa Denko K.K.): [ka] Karenz MOI-EG (Showa Denko Co., Ltd.): [ka]
[0180] In Table 1, the amount of compound (A-2) added represents the parts by mass of compound (A-2) relative to 100 parts by mass of oriented polymer (A-1), and the amount of compound (B-2) added represents the parts by mass of compound (B-2) relative to 100 parts by mass of polymerizable liquid crystal compound. [Table 1]
Claims
1. A polarizing element comprising a substrate, an alignment film, and a polarizing film laminated in this order, The alignment film is Oriented polymer (A-1), and Compound having an active hydrogen-reactive group and an active hydrogen-containing group (A-2) An alignment film formed by curing an alignment film-forming composition comprising: the substrate has at least one polar group selected from the group consisting of a hydroxyl group, a carboxyl group, and an amino group; The polarizing film is Polymerizable liquid crystal compound (B-1) A compound (B-2) having an active hydrogen reactive group, and Dichroic dye (B-3) A polarizing film obtained by curing a composition for forming a polarizing film, comprising: a polarizing element in which the active hydrogen-reactive groups of (A-2) and (B-2) each independently include at least one selected from the group consisting of an epoxy group, a glycidyl group, an oxazoline group, a carbodiimide group, an aziridine group, an imide group, an alkoxysilyl group, an isocyanate group, a thioisocyanate group, and a maleic anhydride group, and the active hydrogen-containing group of (A-2) includes at least one selected from the group consisting of a hydroxyl group, a carboxyl group, an amino group, a mercapto group, a primary amide group, a secondary amide group, and a hydrazide group.
2. 2. The polarizing element according to claim 1, wherein the orientable polymer (A-1) is a polymer having a photoreactive group that undergoes a dimerization reaction.
3. 3. The polarizing element according to claim 1, wherein the orientable polymer (A-1) is a (meth)acrylic polymer.
4. 4. The polarizing element according to claim 1, wherein the weight average molecular weight of the orientable polymer (A-1) is 10,000 or more and 1,000,000 or less.
5. 5. The polarizing element according to claim 1, wherein the compound (A-2) is a silane coupling agent.
6. The polarizing element according to any one of claims 1 to 5, wherein the compound (A-2) is a silane coupling agent containing at least one functional group selected from the group consisting of a primary amino group, a secondary amino group, a hydroxyl group, and a mercapto group.
7. 7. The polarizing element according to claim 1, wherein the content of the compound (A-2) is from 1 part by mass to 30 parts by mass with respect to 100 parts by mass of the orientable polymer (A-1).
8. The polarizing element according to any one of claims 1 to 7, wherein the compound (B-2) further has a polymerizable group.
9. The polarizing element according to claim 8 , wherein the polymerizable group is a (meth)acryloyl group.
10. 10. The polarizing element according to claim 1, wherein the compound (B-2) has at least one isocyanate group and at least one (meth)acryloyl group.
11. The polarizing element according to any one of claims 1 to 10, wherein the content of the compound (B-2) is 0.1 parts by mass or more and 12 parts by mass or less with respect to 100 parts by mass of the polymerizable liquid crystal compound (B-1).
12. The dichroic dye (B-3) is represented by the formula (I): K 1 (-N=N-K 2 ) p -N=N-K 3 (I) [In formula (I), K 1 and K. 3 each independently represents a phenyl group which may be substituted, a naphthyl group which may be substituted, a phenyl benzoate group which may be substituted, or a monovalent heterocyclic group which may be substituted, K 2 represents a p-phenylene group which may have a substituent, a naphthalene-1,4-diyl group which may have a substituent, a 4,4'-stilbenylene group which may have a substituent, or a divalent heterocyclic group which may have a substituent, p represents an integer of 0 to 4, and when p is an integer of 2 or more, a plurality of K 2 may be the same or different, and the -N=N- bond may be replaced with a -C=C-, -COO-, -NHCO-, or -N=CH- bond so long as the compound exhibits absorption in the visible region. The polarizing element according to any one of claims 1 to 11, comprising a compound represented by the formula:
13. 13. The polarizing element according to claim 1, wherein the polymerizable liquid crystal compound (B-1) is a liquid crystal compound exhibiting smectic liquid crystallinity.
14. The polarizing element according to any one of claims 1 to 13, wherein the thickness of the substrate is 1 µm or more and 10 µm or less.
15. 15. The polarizing element according to claim 1, further comprising an overcoat layer on the surface of the polarizing film opposite to the alignment film.
16. A method for producing a polarizing element in which a substrate, an alignment film, and a polarizing film are laminated adjacent to each other in this order, comprising the steps of: (1) A process of forming a coating film of an alignment film-forming composition containing an alignment polymer (A-1) and a compound (A-2) having an active hydrogen reactive group and an active hydrogen-containing group on a substrate having at least one polar group selected from the group consisting of a hydroxyl group, a carboxyl group, and an amino group, and drying the coating film to react the active hydrogen reactive group of the compound (A-2) with the polar group of the substrate to form a bond; (2) forming an alignment layer by subjecting the dried coating film obtained in step (1) to a rubbing treatment or light irradiation; (3) forming a coating film of a composition for forming a polarizing film, which comprises a polymerizable liquid crystal compound (B-1), a compound having an active hydrogen reactive group (B-2), and a dichroic dye (B-3), on the alignment film obtained in the step (2), and drying the coating film; and (4) A step of curing the polymerizable liquid crystal compound (B-1) and the dichroic dye (B-3) in the dried coating film obtained in the step (3) in an aligned state to form a polarizing film. the active hydrogen-reactive groups possessed by (A-2) and (B-2) each independently comprise at least one selected from the group consisting of an epoxy group, a glycidyl group, an oxazoline group, a carbodiimide group, an aziridine group, an imide group, an alkoxysilyl group, an isocyanate group, a thioisocyanate group, and a maleic anhydride group, and the active hydrogen-containing group possessed by (A-2) comprises at least one selected from the group consisting of a hydroxyl group, a carboxyl group, an amino group, a mercapto group, a primary amide group, a secondary amide group, and a hydrazide group.
17. The method according to claim 16, further comprising the step of forming an overcoat layer on the polarizing film formed in step (4).
18. A flat panel display comprising the polarizing element according to any one of claims 1 to 15.
19. A flexible display material comprising the polarizing element according to any one of claims 1 to 15.
Citation Information
Patent Citations
Polarization element, circularly polarizing plate, and method of manufacturing those
JP2017102479A
Liquid crystal composition, polymer liquid crystal compound, light absorbing anisotropic film, laminate and image display device
WO2018124198A1
Composition for forming liquid crystal cured film and use of same
WO2020218104A1